Photosensitive transfer material, method for producing resin pattern, and method for producing circuit wiring

By adding specific components to the photosensitive resin layer of the photosensitive transfer material and performing specific processing, the problem of the peeling sheet adhering to the device is solved, and a more efficient process flow and product quality is achieved.

CN115335771BActive Publication Date: 2025-03-25FUJIFILM CORP
View PDF 40 Cites 0 Cited by

Patent Information

Application Number
CN202080098703.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2020-12-25
Publication Date
2025-03-25
Estimated Expiration
2040-12-25

AI Technical Summary

Technical Problem

In the process of photosensitive transfer material, the peeling sheet is prone to adhere to the device, resulting in a problem of the pipe being blocked and the peeling sheet being reattached to the manufactured wiring substrate.

Method used

By adding an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator to the photosensitive resin layer, and processing it with an aqueous monoethanolamine solution after exposure, the swelling ratio and peeling time of the cured layer are controlled to reduce the adhesion of the peeling sheet.

Benefits of technology

It effectively reduces the adhesion of the stripping sheet in the device, reduces the risk of pipe blockage and re-adhesion of the stripping sheet, and improves the adaptability and efficiency of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115335771B_ABST
    Figure CN115335771B_ABST
Patent Text Reader

Abstract

The present invention provides a photosensitive transfer material, a method for manufacturing a resin pattern, and a method for manufacturing a circuit wiring. The photosensitive transfer material has a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound, and a photopolymerization initiator on a temporary support. The photosensitive resin layer is attached to a transfer substrate and the unit is mJ / cm 2 After the photosensitive resin layer is exposed to light, when 10 μL of a 10% by mass aqueous solution of monoethanolamine at 50° C. is dropped onto the surface of the cured layer with the temporary support peeled off, the swelling ratio of the cured layer in the normal direction of the transferred substrate from the start of dropping of the 10% by mass aqueous solution of monoethanolamine to the time point 10 seconds after the drop is 103% or less, wherein Eb is an exposure amount of a level showing that the residual film after exposure and development with a 15-step step wedge has a residual thickness of ±1% of the thickness of the photosensitive resin layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photosensitive transfer material, a method for manufacturing a resin pattern, and a method for manufacturing a circuit wiring. Background Art

[0002] In a display device (organic electroluminescent (EL) display device, liquid crystal display device, etc.) having a touch panel such as an electrostatic capacitive input device, an electrode pattern of a sensor corresponding to a visible portion, a peripheral wiring portion, and a conductive layer pattern such as wiring for extracting the wiring portion are provided inside the touch panel. In the formation of the patterned layer, a photosensitive resin composition patterned by exposure and development is generally used. In addition, from the perspective of the small number of steps required to obtain a desired pattern shape, a method (so-called transfer method) using a photosensitive transfer material having a photosensitive resin layer is also provided.

[0003] In the case of the transfer method, the following method is widely used: a photosensitive transfer material is bonded to a transfer substrate, a photosensitive layer is transferred to the transfer substrate, and the photosensitive layer is irradiated with light through a mask having a desired pattern, and then developed. After development, the transfer substrate is usually etched using the formed cured pattern as a mask to form wiring, and then the cured pattern is peeled off to obtain a wiring pattern.

[0004] As a technology using a photosensitive transfer material, for example, a technology using a dry film formed by layering a photosensitive resin composition is disclosed (for example, refer to Japanese Patent Publication No. 2004-184714), wherein the photosensitive resin composition is a resist cured by exposing both sides of a photosensitive resin composition layer having a thickness of 35 to 60 μm to 7 exposure levels using a Stouffer 21-step plate, and the initial swelling ratio after 30 minutes after immersion in a 1 wt % sodium carbonate aqueous solution at 21° C. is 120% or less, and the final swelling ratio is 150 to 200%, and the immersion time until the final swelling ratio is reached is 130 minutes or less. In the above-mentioned publication, it is set as excellent in peelability, etc. Summary of the invention

[0005] Technical issues to be solved by the invention

[0006] In the case of forming wiring using a dry film cured by exposure as described in Japanese Patent Publication No. 2004-184714, a method of stripping the resist by swelling the resist with a high-temperature alkali solution is sometimes used. The stripped resist tends to remain directly in the liquid as a stripping sheet. If the stripping sheet remains in the liquid, the stripping sheet is retained in the device, adheres to the device and gradually accumulates, and as a result, sometimes becomes a cause of clogging of the piping, liquid feeding load, etc. In addition, the stripping sheet may also be attached to the manufactured wiring substrate. Therefore, a device for removing the stripping sheet in the liquid by filtering or the like is set in the device to reduce the remaining stripping sheet in the liquid.

[0007] However, when the release sheet is a soft gel-like material, the processing speed based on filtration or the like tends to be significantly reduced. In addition, depending on the situation, it may cause clogging of the piping in the filter device or the like, or conversely, the release sheet may be deformed by the filtration pressure and pass through the filter device or the like without being filtered. Therefore, the release sheet preferably has a hardness that is not easy to adhere to the inside of the device. In addition, the hardness of the release sheet is required to be stably maintained in the liquid regardless of process changes.

[0008] The present invention has been accomplished in view of the above circumstances.

[0009] An object of one embodiment of the present invention is to provide a photosensitive transfer material that reduces the adhesion of a peeled release sheet in a device in a step of peeling off a patterned photosensitive transfer material.

[0010] Another embodiment of the present invention aims to provide a method for producing a resin pattern using a photosensitive transfer material that reduces the adhesion of a peeling sheet in the device in the step of peeling off the patterned photosensitive transfer material.

[0011] Another embodiment of the present invention aims to provide a method for manufacturing circuit wiring using a photosensitive transfer material, which reduces the adhesion of a peeling sheet in a device in the step of peeling off the patterned photosensitive transfer material.

[0012] Means for solving technical problems

[0013] Specific solutions to the problem include the following.

[0014] <1> A photosensitive transfer material comprises a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator on a temporary support.

[0015] After the photosensitive resin layer is attached to the transferred substrate and exposed to light with an exposure amount Ep, when 10 μL of a 10% by mass aqueous solution of monoethanolamine at 50°C is dropped onto the surface of the cured layer with the temporary support peeled off, the swelling ratio of the cured layer in the normal direction of the transferred substrate from the start of dropping of the 10% by mass aqueous solution of monoethanolamine to the time point when 10 seconds have passed is less than 103%.

[0016] Ep=2×Eb

[0017] Ep is expressed in mJ / cm 2 The exposure amount in units of mJ / cm 2 After the photosensitive resin layer was attached to the transfer substrate, a high-pressure mercury lamp was used through a mask with 15-step wedges at an illumination of 20 mW / cm 2 The exposure was performed at an exposure amount of the order of ±1% of the thickness of the photosensitive resin layer, showing that the remaining film after the temporary support was peeled off and developed had a remaining thickness.

[0018] <2> according to <1> The photosensitive transfer material, wherein:

[0019] The swelling ratio of the cured layer in the normal direction of the transfer substrate at the time point when 20 seconds had passed since the start of dripping was 105% or less.

[0020] <3> according to <1> or <2> The photosensitive transfer material, wherein:

[0021] The time t in seconds from the time when at least the cured layer and the transfer substrate after exposure are immersed in a 10 mass % aqueous solution of monoethanolamine at 50° C. to the time when the cured layer is completely peeled off from the transfer substrate is completed. 50 and

[0022] The time t in seconds from the time when at least the cured layer and the transfer substrate after exposure are immersed in a 10 mass % aqueous solution of monoethanolamine at 25° C. to the time when the cured layer is completely peeled off from the transfer substrate is completed. 25 The following formula (A1) and the following formula (A2) are satisfied.

[0023] t 50 ≤60 and t 25 ≤180 (A1)

[0024] 1≤t 25 / t 50 ≤3 (A2)

[0025] <4> A photosensitive transfer material comprises a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator on a temporary support.

[0026] After the photosensitive resin layer is attached to the transfer substrate and exposed to light with an exposure amount Ep, when at least the cured layer and the transfer substrate are immersed in a 10% by weight aqueous solution of monoethanolamine at 25°C with the temporary support peeled off, the cured layer is peeled off from the transfer substrate autonomously.

[0027] Ep=2×Eb

[0028] Ep is expressed in mJ / cm 2 The exposure amount in units of mJ / cm 2 After the photosensitive resin layer was attached to the transfer substrate, a high-pressure mercury lamp was used through a mask with 15-step wedges at an illumination of 20 mW / cm 2 The exposure was performed at an exposure amount of the order of ±1% of the thickness of the photosensitive resin layer, showing that the remaining film after the temporary support was peeled off and developed had a remaining thickness.

[0029] <5> according to <4> The photosensitive transfer material, wherein:

[0030] The cured layer is peeled off from the transfer substrate by itself, and is curled with the side of the cured layer opposite to the side facing the transfer substrate as the inner side.

[0031] <6> according to <4> or <5> The photosensitive transfer material, wherein:

[0032] During immersion, the time from the time when at least the cured layer and the transfer substrate are immersed to the time when the cured layer starts to peel off autonomously from the transfer substrate is within 300 seconds.

[0033] <7> A photosensitive transfer material comprises a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator on a temporary support.

[0034] After the photosensitive resin layer is attached to the transfer substrate and exposed to light at an exposure amount Ep, the time t from the time when at least the cured layer and the transfer substrate are immersed in a 10 mass % aqueous solution of monoethanolamine at 50° C. to the time when the cured layer is completely peeled off from the transfer substrate is 1. fr and

[0035] After the photosensitive resin layer is attached to the transfer substrate and exposed to light at an exposure amount Ep, with the temporary support peeled off, the time t from the time when at least the cured layer and the transfer substrate are immersed in a 50° C. aqueous solution into which carbon dioxide is blown at a flow rate of 46 mL / min for 160 seconds in 1000 mL of a 10 mass % aqueous solution of monoethanolamine to the time when the cured layer is peeled off from the transfer substrate is completed. fa The following formula (B1) is satisfied.

[0036] t fa ≤t fr ×1.5 (B1)

[0037] Ep=2×Eb

[0038] Ep is expressed in mJ / cm 2 The exposure amount in units of mJ / cm 2 After the photosensitive resin layer was attached to the transfer substrate, a high-pressure mercury lamp was used through a mask with 15-step wedges at an illumination of 20 mW / cm 2 The exposure was performed at an exposure amount of the order of ±1% of the thickness of the photosensitive resin layer, showing that the remaining film after the temporary support was peeled off and developed had a remaining thickness.

[0039] <8> according to <1> to <7> The photosensitive transfer material described in any one of the preceding claims, wherein

[0040] The polymerizable compound includes a bifunctional or higher-functional compound having two or more ethylenically unsaturated groups in one molecule.

[0041] <9> according to <1> to <8> The photosensitive transfer material described in any one of the preceding claims, wherein

[0042] The polymerizable compound includes a bifunctional ethylenically unsaturated compound having two ethylenically unsaturated groups in one molecule and a trifunctional ethylenically unsaturated compound having three ethylenically unsaturated groups in one molecule, and the content ratio of the trifunctional ethylenically unsaturated compound is 10% by mass or more relative to the total amount of the polymerizable compound.

[0043] <10> according to <8> or <9> The photosensitive transfer material, wherein:

[0044] The difunctional or higher-functional compound having two or more ethylenically unsaturated groups in one molecule includes a compound represented by the following formula (1).

[0045] [Chemical formula 1]

[0046]

[0047] In formula (1), R 1 and R 2 Each independently represents a hydrogen atom or a methyl group, and A represents C 2 H 4 , B represents C 3 H 6 .n 1 and n 3 Each independently represents an integer from 1 to 39, and n 1 +n s is an integer from 2 to 40. 2 and n 4 Each independently represents an integer from 0 to 29, and n 2 +n 4 is an integer of 0 to 30. The arrangement of the repeating units of -(AO)- and -(BO)- may be random or block. When the arrangement is block, either -(AO)- or -(BO)- may be on the biphenyl side.

[0048] <11> according to <9> The photosensitive transfer material, wherein:

[0049] The content ratio of the trifunctional ethylenically unsaturated compound is 30% by mass or more based on the total amount of the polymerizable compound.

[0050] <12> according to <1> to <11> The photosensitive transfer material described in any one of the preceding claims, wherein

[0051] The thickness of the photosensitive resin layer is 5 μm or more.

[0052] <13> A method for manufacturing a resin pattern, comprising:

[0053] make <1> to <12> A step of laminating the photosensitive transfer material described in any one of the above to a transferred substrate and disposing a photosensitive resin layer on the transferred substrate;

[0054] A step of exposing the photosensitive resin layer to a pattern; and

[0055] A step of developing the photosensitive resin layer to form a resin pattern.

[0056] <14> A method for manufacturing a circuit wiring, comprising:

[0057] make <1> to <12> A step of laminating the photosensitive transfer material described in any one of the above to a transfer substrate having a conductive layer, and disposing a photosensitive resin layer on the transfer substrate;

[0058] A process of exposing the photosensitive resin layer to a pattern;

[0059] A step of developing the photosensitive resin layer to form a resin pattern;

[0060] a step of etching the conductive layer in a region where the resin pattern is not disposed to form circuit wiring; and

[0061] The process of peeling off and removing the resin pattern.

[0062] Effects of the Invention

[0063] According to one embodiment of the present invention, there is provided a photosensitive transfer material capable of reducing the adhesion of a peeled release sheet in a device in a step of peeling off a patterned photosensitive transfer material.

[0064] According to another embodiment of the present invention, there is provided a method for manufacturing a resin pattern using a photosensitive transfer material that reduces the in-device adhesion of a peeling sheet in a step of peeling off a patterned photosensitive transfer material.

[0065] According to another embodiment of the present invention, there is provided a method for manufacturing a circuit wiring using a photosensitive transfer material, in which the adhesion of a peeled release sheet in a device is reduced in a step of peeling off a patterned photosensitive transfer material. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 This is a schematic cross-sectional view showing an example of the structure of a photosensitive transfer material.

[0067] Figure 2 This is a schematic plan view showing an example of a pattern of a mask for manufacturing a touch panel.

[0068] Figure 3 This is a schematic plan view showing another example of the pattern of the mask for manufacturing a touch panel. DETAILED DESCRIPTION

[0069] Hereinafter, the contents of the present disclosure will be described in detail.

[0070] Although the description of the constituent elements described below may be based on representative embodiments of the present disclosure, the present disclosure is not limited to these embodiments.

[0071] In the present invention, "to" indicating a numerical range is used to mean that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0072] In the present invention, in the numerical ranges recorded in stages, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of other numerical ranges recorded in stages. In addition, in the numerical ranges recorded in the present invention, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.

[0073] In the present specification, when the amount of each component in a composition is mentioned, unless otherwise specified, when a plurality of components corresponding to each component are present in the composition, the amount refers to the total amount of the plurality of components present in the composition.

[0074] The term "solid content" in the present specification refers to components other than the solvent, and liquid components such as low molecular weight components other than the solvent are also included in the "solid content" in the present specification.

[0075] In the present specification, the term "solvent" is used to mean water, an organic solvent, and a mixed solvent of water and an organic solvent.

[0076] In addition, in this specification, both or either of acrylic acid and methacrylic acid may be expressed as "(meth)acrylic acid". For example, "(meth)acrylic acid" includes both acrylic acid and methacrylic acid, and "(meth)acryloyl" includes both acryloyl and methacryloyl.

[0077] “(Tri / tetra / penta / hexa) (meth)acrylate” is a concept including tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate and hexa(meth)acrylate, and “(tri / tetra) (meth)acrylate” is a concept including tri(meth)acrylate and tetra(meth)acrylate.

[0078] In the present specification, "alkali-soluble" means that the solubility of sodium carbonate in 100 g of a 1 mass % aqueous solution at 22°C is 0.1 g or more.

[0079] In this specification, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0080] In the present invention, compounds not explicitly described as substituted or unsubstituted may have any substituent within a range not impairing the effects of the present invention.

[0081] In addition, in the present invention, a combination of preferred embodiments is a more preferred embodiment.

[0082] The weight average molecular weight (Mw) in the present invention is measured by gel permeation chromatography (GPC).

[0083] GPC used HLC-8220GPC (manufactured by TOSOH CORPORATION). As columns, three columns, TSKgeL Super HZ2000, TSKgeL Super HZ4000, and TSKgeL Super HZ-H (all manufactured by TOSOH CORPORATION, 4.6 mm×15 cm), were connected in series. As eluent, NMP (N-methylpyrrolidone) was used. The sample concentration was set to 0.3% by mass, the flow rate was set to 0.35 ml / min, the sample injection volume was set to 10 μL, the measurement temperature was set to 40°C, and as a detector, an RI (Refractive Index) detector (differential refractive index detector) was used. In addition, a calibration curve was prepared from six samples of "TSK standard, polystyrene" manufactured by TOSOH CORPORATION: "F-80", "F-20", "F-4", "F-2", "A-5000", and "A-1000".

[0084] <Photosensitive transfer material>

[0085] The photosensitive transfer material of the present invention has a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator on a temporary support. When the photosensitive resin layer is provided for pattern formation, a cured portion (i.e., a resin pattern) can be formed by exposing the photosensitive resin layer as a pattern and developing it, and the formed resin pattern can be stripped with a stripping solution. The photosensitive transfer material of the present invention is preferably provided as a material for a process of stripping using a stripping solution.

[0086] In the photosensitive transfer material of the present invention, the cured layer formed by curing the photosensitive resin layer by exposure has the characteristics described in the following (1), (2) or (3).

[0087] (1) The swelling ratio of the cured layer during peeling is below a prescribed value.

[0088] (2) The cured layer is peeled off autonomously during peeling. Preferably, the cured layer is peeled off autonomously, for example, as a small peeling piece.

[0089] (3) The change in the peeling speed due to fatigue of the peeling liquid is small.

[0090] Furthermore, the photosensitive transfer material of the present invention may further include other layers such as a thermoplastic resin layer and an intermediate layer as necessary.

[0091] Conventionally, for example, Japanese Patent Application Laid-Open No. 2004-184714 provides a dry film formed by layering a photosensitive resin composition in which the initial swelling ratio, final swelling ratio, and immersion time until the final swelling ratio are set within specific ranges after immersing an exposed cured resist in a sodium carbonate aqueous solution.

[0092] For example, when a dry film is used to form wiring on a transferred substrate, as described above, the resist (resin pattern in a solidified state) that remains on the transferred substrate after the wiring is formed is peeled off. When peeling off the resist, a method is usually adopted in which a high-temperature alkaline solution is used as a stripping liquid to swell the resist and then peel it off. Sometimes the stripped resist remains in the stripping liquid as a stripping sheet. Depending on the properties of the stripping sheet remaining in the stripping liquid, it is not removed by filtering and remains in the stripping liquid, and the remaining stripping sheet adheres to the device and accumulates, thereby causing clogging of the piping and the like and a decrease in the filtering function. In addition, there is also the possibility of reattachment to the manufactured wiring substrate. In particular, when the stripping sheet is a soft material such as a gel, it is clearly visible.

[0093] Based on the results of the above research, the following insights were obtained.

[0094] When the swelling amount is large when peeling off the resist that solidifies like a pattern (i.e., the resin pattern as the solidified part), it is known that the behavior of the peeled resist is the same as the soft gel-like material as described above. That is, it is known that if the swelling amount of the peeled resin pattern is large, it is easy to adhere to the device, accumulate and easily cause various problems. On the other hand, in the resin pattern with a small swelling amount, if it is peeled off with a stripping liquid, it is easy to deform into a winding shape, etc., and the resin pattern gathers into small pieces and easily obtains good filterability. In addition, even if the resin pattern with a small swelling amount becomes a state (i.e., fatigue state) in which the stripping liquid as an alkali solution absorbs carbon dioxide and is neutralized, the properties of the resin pattern itself change little, so it can maintain a stable solidified state without changing the process, and it is difficult to damage the filterability, etc. As described above, by maintaining swelling by suitability, the process suitability becomes good, and as a result, the adhesion of the stripping sheet in the device can be suppressed to a small extent.

[0095] In summary, the photosensitive transfer material of the present invention includes the following three aspects (first aspect, second aspect and third aspect):

[0096] In addition, the first aspect corresponds to the above-mentioned feature (1), the second aspect corresponds to the above-mentioned feature (2), and the third aspect corresponds to the above-mentioned feature (3).

[0097] [First method]

[0098] The first embodiment of the present invention relates to a photosensitive transfer material, which has a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator on a temporary support. After the photosensitive resin layer is bonded to a transferred substrate and exposed to an exposure amount Ep, when 10 μL of a 10% by mass aqueous solution of monoethanolamine (hereinafter sometimes abbreviated as "MEA") at 50°C is dropped onto the surface of the cured layer with the temporary support peeled off, the swelling ratio in the normal direction of the transferred substrate in the cured layer from the start of dropping of the 10% by mass aqueous solution of monoethanolamine (MEA) to the time point when 10 seconds have passed (hereinafter sometimes referred to as the "swelling ratio after 10 seconds") is less than 103%.

[0099] Ep=2×Eb

[0100] In addition, the cured layer refers to an exposed region in the photosensitive resin layer exposed with an exposure amount Ep.

[0101] Ep is expressed in mJ / cm 2 The exposure amount in units.

[0102] Eb is expressed as follows: mJ / cm 2 After the photosensitive resin layer was attached to the transfer substrate, a high-pressure mercury lamp was used through a mask with 15-step wedges at an illumination of 20 mW / cm 2 The exposure is performed at an exposure amount of the order of ±1% (ie, 0.99t to 1.01t) of the thickness (t) of the photosensitive resin layer so that the residual film after the temporary support is peeled off and developed has a residual thickness.

[0103] If the swelling ratio after 10 seconds is 103% or less and is suppressed to be small, the swelling of the cured layer after exposure due to contact with the stripping liquid is suppressed to be small, and the swelling rate also tends to be slow. Therefore, the photosensitive transfer material involved in the first embodiment is not easy to gel, is not easy to re-attach after peeling, and the accumulation in the device is also suppressed to be small. As a result, in the case of peeling and removing the resin pattern formed by developing the exposed photosensitive transfer material, the photosensitive transfer material of the present invention has good process suitability.

[0104] In addition, the lamination of the photosensitive resin layer and the transferred substrate is described in the "lamination step" in the method for producing a resin pattern or circuit wiring described later. The exposure of the photosensitive resin layer with the exposure amount Ep is described in the "exposure step" in the method for producing a resin pattern or circuit wiring described later.

[0105] The step wedge is a density step in which a plurality of steps (regions) in which the density changes in a stepwise manner with a predetermined density difference are arranged in one direction. In the present invention, a step wedge having 15 steps can be used.

[0106] The exposure amount Ep is determined based on the exposure amount Eb.

[0107] Eb is determined by the following method. That is,

[0108] The transferred substrate and the photosensitive transfer material are laminated together, and a step wedge is arranged on the temporary support of the photosensitive transfer material laminated on the transferred substrate. 2 The high pressure mercury lamp was used through a step wedge with an exposure of 180 mJ / cm 2 The photosensitive resin layer is irradiated with ultraviolet rays. The temporary support after irradiation is peeled off and developed with a 0.9 mass % aqueous solution of sodium carbonate at 25°C for 30 seconds. Thereafter, the thickness of the cured layer (remaining film thickness) in the region corresponding to each step of the step wedge is measured. The number of steps within the range of ±1% relative to the thickness of the photosensitive resin layer before development is determined as the remaining film thickness (thickness of the cured layer), and the exposure amount corresponding to the determined number of steps is taken as Eb.

[0109] “From the start of dripping of 10 mass % aqueous solution of monoethanolamine to the time point when 10 seconds have passed” means the period from the start point to the time point when 10 mass % aqueous solution of MEA is dripped onto the surface of the solidified layer (end point).

[0110] The swelling ratio of the solidified layer in the normal direction of the transferred substrate is as follows and is calculated by the following formula: the ratio of the solidified layer in the normal direction parallel to the normal direction of the transferred substrate in the dripping area of ​​the 10 mass % MEA aqueous solution, that is, the thickness of the solidified layer from the dripping of the aqueous solution to the time point when 10 seconds have passed (t 10s ) and the thickness of the solidified layer after irradiation and before the aqueous solution is added (t b ) ratio.

[0111] Regarding the thickness after irradiation and before the aqueous solution is dropped (t b ), select 5 random areas of the solidified layer to measure the thickness, and take it as the average value of the 5 thicknesses. 10s ), add 10 mass % aqueous solution of MEA to the above 5 areas of the solidified layer to form 5 dropping areas, and take the average value of the 5 thicknesses as the average value.

[0112] Swelling ratio after 10 seconds (%) = (t 10s / t b )×100

[0113] The thickness of the solidified layer before and after the dropping of the MEA 10 mass % aqueous solution is a value measured by a non-contact three-dimensional surface profile measuring device, and can be measured using, for example, Zygo NewView6300 manufactured by Zygo Corporation.

[0114] The swelling ratio after 10 seconds is preferably 102% or less, and more preferably 101% or less for the same reason as above. The lower limit of the swelling ratio after 10 seconds is 100%, and it is preferably in a range exceeding 100%.

[0115] In the photosensitive transfer material involved in the first embodiment, the swelling ratio in the normal direction of the transferred substrate in the cured layer at 20 seconds after the drop of the 10 mass % monoethanolamine aqueous solution (hereinafter also referred to as "swelling ratio after 20 seconds") is preferably 105% or less.

[0116] “From the start of dripping of 10 mass % aqueous solution of monoethanolamine to the time point when 20 seconds have passed” means the period from the start point to the time point when 10 mass % aqueous solution of MEA is dripped onto the surface of the solidified layer (end point).

[0117] The swelling ratio of the solidified layer in the normal direction of the transferred substrate is as follows and is calculated by the following formula: the ratio of the solidified layer in the normal direction parallel to the normal direction of the transferred substrate to become a thick film, that is, the thickness of the solidified layer from the drop of the MEA 10 mass % aqueous solution to the time point when 20 seconds have passed (t 20s ) and the thickness of the solidified layer before adding a 10 mass % aqueous solution of MEA after irradiation (t b ) ratio.

[0118] Regarding the thickness after irradiation and before the aqueous solution is dropped (t b ), select 5 random areas of the solidified layer to measure the thickness, and take the average value of the 5 thicknesses. 20s ), add 10 mass % aqueous solution of MEA to the above 5 areas of the solidified layer to form 5 dropping areas, and take the average value of the 5 thicknesses as the average value.

[0119] Swelling ratio after 20 seconds (%) = (t 20s / t b )×100

[0120] The thickness of the solidified layer before and after the dropping of the MEA 10 mass % aqueous solution is a value measured by a non-contact three-dimensional surface profile measuring device, and can be measured using, for example, Zygo NewView6300 manufactured by Zygo Corporation.

[0121] The swelling ratio after 20 seconds is preferably 103% or less, and more preferably 102% or less for the same reason as above. The lower limit of the swelling ratio after 20 seconds is 100%, and it is preferably in a range exceeding 100%.

[0122] When the photosensitive transfer material is laminated on the transferred substrate to form a pattern, it is exposed to an alkali solution at least twice in the process of making the pattern according to the irradiated pattern obvious (the so-called development process) and the process of stripping and removing the pattern (the so-called stripping process). In the development process, alkali development of the uncured part is performed at a low temperature (about 25°C), and in the stripping process, alkali stripping of the cured part is performed at a high temperature (about 50°C). Therefore, in each process, the difference in the swelling rate of the cured layer based on the temperature is preferably large. As described above, by making the swelling rate different according to the temperature, not only the stripping property in the stripping process of alkali stripping is improved, but also the decrease in pattern formation due to unexpected swelling in the developing process of alkali development is suppressed.

[0123] From this point of view, the time t in seconds from the time when at least the cured layer and the transfer substrate after exposure are immersed in a 10 mass % aqueous solution of monoethanolamine at 50° C. to the time when the cured layer is completely peeled off from the transfer substrate is 50 The time t in seconds from the time when at least the cured layer and the transfer substrate after exposure are immersed in a 10 mass % aqueous solution of monoethanolamine at 25° C. to the time when the cured layer is completely peeled off from the transfer substrate is completed. 25 It is preferable to satisfy the following formula (A1) and the following formula (A2).

[0124] t 50 ≤60 seconds and t 25 ≤180 seconds (A1)

[0125] 1≤t 25 / t 50 ≤3 (A2)

[0126] "From the time of immersion to the time when the solidified layer is completely peeled off from the transferred substrate" means that, among at least the solidified layer and the transferred substrate as a whole constituting the photosensitive transfer material after exposure, the time when they are completely immersed in the MEA 10 mass % aqueous solution is taken as the starting point, and the time from the starting point to the time when the solidified layer in the aqueous solution is completely peeled off from the transferred substrate (end point).

[0127] t 50 is 60 seconds or less, preferably 20 seconds or less, and more preferably 15 seconds or less. 50 Preferably, it is 5 seconds or longer.

[0128] t 25is 180 seconds or less, preferably 120 seconds or less, and more preferably 60 seconds or less. 25 Preferably, it is 10 seconds or longer.

[0129] In addition, from the viewpoint of performing alkali development well in a low temperature range and performing alkali stripping well in a high temperature range, t 50 and t 25 It is more preferable to satisfy the following formula (A2-1), and it is even more preferable to satisfy the following formula (A2-2).

[0130] 2≤t 25 / t 50 ≤3 (A2-1)

[0131] 2.5≤t 25 / t 50 ≤3 (A2-2)

[0132] In the photosensitive transfer material according to the first aspect of the present invention, in order to set the swelling ratio of the cured layer after 10 seconds to 103% or less, it is conceivable to control the curing degree of the cured layer. Specific methods for achieving the swelling ratio after 10 seconds are listed below.

[0133] (1) Adjusting the thickness of the photosensitive resin layer (cured layer).

[0134] (2) Adjusting the type and content of the polymerizable compound used in the photosensitive resin layer and the combination when two or more polymerizable compounds are used in combination.

[0135] (3) Adjust the type and content of polymerization initiator.

[0136] (4) Use a chain transfer agent.

[0137] (5) Adjusting the molecular weight, glass transition point and melt viscosity of the binder resin and the polymerizable compound.

[0138] In addition, details of the alkali-soluble resin, polymerizable compound, photopolymerization initiator, etc. in the photosensitive transfer material according to the first embodiment, as well as the temporary support, the photosensitive resin layer, and the transferred substrate, etc., will be described later.

[0139] [Second method]

[0140] The photosensitive transfer material involved in the second embodiment of the present invention has a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator on a temporary support. After the photosensitive resin layer is attached to a transferred substrate and exposed to an exposure amount Ep, when at least the cured layer and the transferred substrate are immersed in a 10% by weight aqueous solution of monoethanolamine (MEA) at 25°C with the temporary support peeled off, the cured layer is peeled off from the transferred substrate autonomously.

[0141] Ep=2×Eb

[0142] Ep is expressed in mJ / cm 2 The exposure amount in units.

[0143] Eb is expressed as follows: mJ / cm 2 After the photosensitive resin layer was attached to the transfer substrate, a high-pressure mercury lamp was used through a mask with 15-step wedges at an illumination of 20 mW / cm 2 The exposure is performed at an exposure amount of the order of ±1% (ie, 0.99t to 1.01t) of the thickness (t) of the photosensitive resin layer so that the residual film after the temporary support is peeled off and developed has a residual thickness.

[0144] The details of Ep and Eb are the same as those in the above-mentioned first embodiment.

[0145] The details of the alkali-soluble resin, polymerizable compound, photopolymerization initiator, etc. in the photosensitive transfer material according to the second embodiment, as well as the temporary support, the photosensitive resin layer, and the transferred substrate, will be described later.

[0146] The self-peeling phenomenon is a phenomenon that occurs when the substrate is immersed in a 10 mass % aqueous solution of MEA and is a phenomenon that occurs in the peeling step of peeling the cured layer from the transferred substrate. The peeling step will be described in detail later.

[0147] The peeling step is a step after laminating the photosensitive resin layer to the transferred substrate and exposing the photosensitive resin layer with the exposure amount Ep. Laminating the photosensitive resin layer to the transferred substrate will be described in the "laminating step" in the method for manufacturing a resin pattern or circuit wiring described later. Exposing the photosensitive resin layer with the exposure amount Ep will be described in the "exposure step" in the method for manufacturing a resin pattern or circuit wiring described later.

[0148] “Self-peeling” means that when the transfer substrate to which the exposed cured layer is attached is immersed in a 10 mass % MEA aqueous solution at 25° C., the cured layer itself is automatically separated and peeled from the transfer substrate without being pulled or otherwise subjected to external forces.

[0149] For example, when the photosensitive resin layer is a negative photosensitive layer, the side of the photosensitive resin layer bonded to the transferred substrate is sometimes attenuated by light when exposed with the exposure amount Ep, and the degree of curing is low, and it is easy to swell when in contact with the MEA 10 mass % aqueous solution. In the negative type, there is a tendency that the side of the photosensitive resin layer close to the temporary support (the side close to the light source during exposure) is easier to cure than the side of the transferred substrate (=the side away from the light source during exposure), and the side of the transferred substrate is more difficult to cure than the side close to the temporary support. In this case, there is a tendency that the cured layer formed by the exposure of the photosensitive resin layer decreases in degree of curing from the side away from the transferred substrate in the layer thickness direction (the side close to the light source during exposure) toward the side close to it, so it is easy to swell, and the film stress caused by swelling of the photosensitive resin layer from the side close to the side away from the transferred substrate acts. As a result, the cured layer can be obtained to be automatically separated from the transferred substrate and then peeled off.

[0150] In the case where the solidified layer is peeled off from the transferred substrate autonomously, there are cases where the solidified layer is peeled off without large deformation and cases where it is peeled off with deformation. In the former, it is easy to obtain a peeling sheet comprising a flat surface. In the latter, it is easy to obtain a peeling sheet having a shape of a curved surface in which the side of the solidified layer with greater swelling (the side opposite to the transferred substrate) is directed outward and the temporary support body side (the side not opposite to the transferred substrate) with less swelling than the transferred substrate side is directed inward (i.e., curled). The latter peeling sheet is rolled up and formed into a cylindrical shape, for example, so that small pieces are easily obtained. As in the latter, by making the peeling sheet into a small piece, it is easy to remove the peeling sheet (precipitation, filtration, etc.).

[0151] The cured layer in the second aspect of the present invention is preferably a layer that is peeled off autonomously from the transfer substrate and is curled with the side of the cured layer opposite to the side facing the transfer substrate facing the transfer substrate facing the inside.

[0152] In the photosensitive transfer material involved in the second embodiment of the present invention, when immersed in a 10 mass % aqueous solution of MEA, the time from the time of immersion of at least the solidified layer and the transferred substrate to the time when the solidified layer starts to peel off autonomously from the transferred substrate (hereinafter referred to as the autonomous peeling time) is preferably within 300 seconds. That is, the time from the immersion to the occurrence of autonomous peeling is preferably within 300 seconds. The autonomous peeling time of less than 300 seconds means that, for example, when there is a difference in the degree of swelling of the solidified layer on the side opposite to the transferred substrate and the side not opposite to it, it is easy to generate film stress and obtain the film properties of small flakes of peeling sheets.

[0153] “At least the cured layer and the transferred substrate are immersed” means the time when at least the cured layer and the transferred substrate constituting the photosensitive transfer material after exposure are completely immersed in the MEA 10 mass % aqueous solution.

[0154] The “time point when the cured layer starts to peel off autonomously from the transfer substrate” means the time point when at least a part of the edge of the cured layer after exposure in a state immersed in a 10 mass % aqueous solution of MEA separates from the transfer substrate and floats up.

[0155] The self-peeling time is preferably 280 seconds or less, and may be 230 seconds or less, or 200 seconds or less, for the same reason as described above.

[0156] The self-peeling time was measured by placing a 10 mass % MEA solution in a water bath and adjusting the temperature. After the sample was immersed in the solution, the time from the surface of the transferred substrate to the time when the cured layer began to float was measured by visual observation. The measurement was performed three times, and the average value was taken as the peeling time.

[0157] In the photosensitive transfer material according to the second aspect of the present invention, in order to autonomously peel the cured layer from the transferred substrate, it is considered to control the swelling properties of the cured layer to be different between the side facing the transferred substrate and the side not facing the transferred substrate. Specific methods for achieving autonomous peeling are listed below.

[0158] (1) Adjusting the thickness of the photosensitive resin layer (cured layer).

[0159] (2) Adjusting the type and content of the polymerizable compound used in the photosensitive resin layer and the combination when two or more polymerizable compounds are used in combination.

[0160] (3) Adjust the type and content of polymerization initiator.

[0161] (4) Use a chain transfer agent.

[0162] In addition, details of the alkali-soluble resin, polymerizable compound, photopolymerization initiator, etc. in the photosensitive transfer material according to the second embodiment, as well as the temporary support, the photosensitive resin layer, and the transferred substrate, etc., will be described later.

[0163] [Third Method]

[0164] The photosensitive transfer material according to the third aspect of the present invention has a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator on a temporary support, and the time t fr and time t fa The following formula (B1) is satisfied.

[0165] tfa ≤t fr ×1.5 (B1)

[0166] "Time t fr ” refers to the time (seconds) from the time when at least the cured layer and the transferred substrate are immersed in a 10% by mass aqueous solution of monoethanolamine at 50° C. to the time when the cured layer is completely peeled off from the transferred substrate after the photosensitive resin layer is attached to the transferred substrate and exposed to light with an exposure amount Ep, with the temporary support peeled off.

[0167] "Time t fa "" means that after the photosensitive resin layer is attached to the transfer substrate and the photosensitive resin layer is exposed at an exposure amount Ep, carbon dioxide (CO 2) is blown into the transfer substrate at a flow rate of 46 mL / min from at least the cured layer and the transfer substrate immersed in 1000 mL of a 10% by mass aqueous solution of monoethanolamine with the temporary support peeled off. 2 ) The time (in seconds) from the time when the 50° C. aqueous solution was added for 160 seconds to the time when the cured layer was completely peeled off from the transferred substrate.

[0168] Ep=2×Eb

[0169] Ep is expressed in mJ / cm 2 The exposure amount in units.

[0170] Eb is expressed as follows: mJ / cm 2 After the photosensitive resin layer was attached to the transfer substrate, a high-pressure mercury lamp was used through a mask with 15-step wedges at an illumination of 20 mW / cm 2 The exposure is performed at an exposure amount of the order of ±1% (ie, 0.99t to 1.01t) of the thickness (t) of the photosensitive resin layer so that the residual film after the temporary support is peeled off and developed has a residual thickness.

[0171] The details of Ep and Eb are the same as those in the above-mentioned first embodiment.

[0172] The details of the alkali-soluble resin, polymerizable compound, photopolymerization initiator, etc. in the photosensitive transfer material according to the third aspect, as well as the temporary support, the photosensitive resin layer, and the transferred substrate, will be described later.

[0173] t fa and t frThe relationship satisfying the above formula (B1) means that when a cured resin pattern is peeled off from a transferred substrate using a degraded alkali solution (stripping solution), the swelling property when in contact with the stripping solution and the time required for stripping (stripping time) do not change significantly compared to when a cured resin pattern is peeled off from a transferred substrate using a new alkali solution (stripping solution) before deterioration. That is, the change in the stripping time before and after the deterioration of the stripping solution is preferably small.

[0174] That is, a photosensitive transfer material with a small change in swelling property and peeling time due to fatigue of the stripping solution shows good process suitability when a cured layer (resin pattern) is formed by peeling off the exposed photosensitive resin layer and developing it. This is because a photosensitive transfer material with a large change in swelling property and peeling time due to fatigue of the stripping solution is difficult to operate stably without damaging the adhesion of the stripping sheet in the device.

[0175] For the same reasons as above, it is preferred that t fa and t fr The relationship satisfies the following formula (B1-1) or the following formula (B1-2).

[0176] t fa ≤t fr ×1.4 (B1-1)

[0177] t fa ≤t fr ×1.3 (B1-2)

[0178] The peeling of the cured layer from the transferred substrate is a phenomenon that occurs in the peeling liquid and in a peeling step described later. The peeling step will be described in detail later.

[0179] The peeling step is a step after laminating the photosensitive resin layer to the transferred substrate and exposing the photosensitive resin layer with the exposure amount Ep. Laminating the photosensitive resin layer to the transferred substrate will be described in the "laminating step" in the method for manufacturing a resin pattern or circuit wiring described later. Exposing the photosensitive resin layer with the exposure amount Ep will be described in the "exposure step" in the method for manufacturing a resin pattern or circuit wiring described later.

[0180] Time t fr The "time point when at least the cured layer and the transferred substrate are immersed in a 10 mass % aqueous solution of monoethanolamine at 50°C" refers to the time point (immersion end point) when at least the cured layer and the transferred substrate as a whole constituting the photosensitive transfer material after exposure are completely immersed in the 10 mass % aqueous solution of MEA.

[0181] Time t frThe term “until the solidified layer is peeled off from the transferred substrate” means the time point (peeling completion point) when the solidified layer is peeled off from the transferred substrate in a 10 mass % aqueous solution of MEA and becomes two completely separated solids.

[0182] "Time t fr "" indicates the time from the end point of immersion to the end point of stripping when using a new alkali solution (stripping solution) before deterioration, that is, the time required for stripping under normal conditions.

[0183] “A 50° C. aqueous solution into which carbon dioxide was blown at a flow rate of 46 mL / min for 160 seconds into 1000 mL of a 10 mass % aqueous solution of monoethanolamine” (hereinafter also referred to as MEA fatigue solution) is a fatigue solution simulating a stripping solution deteriorated by use.

[0184] The alkaline solution used as the stripping solution may be subject to various factors such as neutralization fatigue of carbonates due to absorption of carbon dioxide in the atmosphere and pH drop. However, in the present invention, the MEA fatigue solution into which a predetermined amount of carbon dioxide is blown is used as a representative example of fatigue solution.

[0185] Time t fa The "time point when at least the cured layer and the transferred substrate are immersed in a 50°C aqueous solution into which carbon dioxide is blown at a flow rate of 46 mL / min for 160 seconds per 1000 mL of a 10 wt % aqueous solution of monoethanolamine" means the end point of immersion when at least the cured layer and the entire transferred substrate constituting the photosensitive transfer material after exposure are completely immersed in the MEA fatigue solution.

[0186] Time t fa The term “until the solidified layer is peeled off from the transferred substrate” means the time point (peeling end point) when the solidified layer is peeled off from the transferred substrate in the MEA fatigue liquid and becomes two solid bodies that are completely separated from each other.

[0187] "Time t fa "" indicates the time from the end point of immersion to the end point of peeling when using MEA fatigue solution, that is, the time required for the peeling solution to peel in a fatigued state.

[0188] In order to realize the above formula (B1) in the photosensitive transfer material according to the third aspect of the present invention, it is conceivable to control so as to increase the swelling property to the MEA fatigue liquid. Specific methods for realizing the above formula (B1) are listed below.

[0189] (1) Adjusting the type and content of the polymerizable compound used in the photosensitive resin layer and the combination when using two or more polymerizable compounds in combination.

[0190] (2) Adjusting the molecular weight, acid value, and hydrophilicity and hydrophobicity of the binder resin and the polymerizable compound.

[0191] The photosensitive transfer material according to the first aspect of the present invention is more preferably in the following aspects.

[0192] A photosensitive transfer material according to another aspect of the present invention comprises a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound, and a photopolymerization initiator on a temporary support.

[0193] After the photosensitive resin layer is attached to the transferred substrate and exposed to light with an exposure amount Ep, when 10 μL of a 10 mass % aqueous solution of MEA at 50°C is dropped onto the surface of the cured layer, the swelling ratio of the cured layer in the normal direction of the transferred substrate from the start of dripping of the 10 mass % aqueous solution of monoethanolamine (MEA) to the time point 10 seconds later (swelling ratio after 10 seconds) is within a range of less than 103%, and when at least the cured layer and the transferred substrate are immersed in a 10 mass % aqueous solution of MEA at 25°C, the cured layer peels off from the transferred substrate autonomously.

[0194] Ep=2×Eb

[0195] In addition, the details of Ep and Eb are as described above.

[0196] A photosensitive transfer material according to another aspect of the present invention comprises a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound, and a photopolymerization initiator on a temporary support.

[0197] After the photosensitive resin layer is bonded to the transferred substrate and exposed to an exposure amount Ep, when 10 μL of a 10 wt % aqueous solution of MEA at 50° C. is dropped onto the surface of the cured layer, the swelling ratio of the cured layer in the normal direction of the transferred substrate from the start of dropping of the 10 wt % aqueous solution of monoethanolamine (MEA) to the time point 10 seconds later (swelling ratio after 10 seconds) is within a range of less than 103%, and satisfies the following formula (B1).

[0198] Ep=2×Eb

[0199] t fa ≤t fr ×1.5 (B1)

[0200] In addition, Ep, Eb, time t fr and time t fa The details are as described above.

[0201] A photosensitive transfer material according to another aspect of the present invention comprises a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound, and a photopolymerization initiator on a temporary support.

[0202] After the photosensitive resin layer is attached to the transfer substrate and exposed to light with an exposure amount Ep, when at least the cured layer and the transfer substrate are immersed in a 10% by mass aqueous solution of monoethanolamine at 25°C, the cured layer peels off from the transfer substrate autonomously and satisfies the following formula (B1).

[0203] Ep=2×Eb

[0204] t fa ≤t fr ×1.5 (B1)

[0205] In addition, Ep, Eb, time t fr and time t fa The details are as described above.

[0206] A photosensitive transfer material according to another aspect of the present invention comprises a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound, and a photopolymerization initiator on a temporary support.

[0207] After the photosensitive resin layer is attached to the transferred substrate and exposed to an exposure amount Ep, when 10 μL of a 10 mass % aqueous solution of MEA at 50°C is dropped onto the surface of the cured layer, the swelling ratio of the cured layer in the normal direction of the transferred substrate from the start of dripping of the 10 mass % aqueous solution of monoethanolamine (MEA) to the time point 10 seconds later (swelling ratio after 10 seconds) is within a range of less than 103%, and when at least the cured layer and the transferred substrate are immersed in a 10 mass % aqueous solution of MEA at 25°C, the cured layer peels off from the transferred substrate autonomously and satisfies the following formula (B1).

[0208] Ep=2×Eb

[0209] t fa ≤t fr ×1.5 (B1)

[0210] In addition, Ep, Eb, time t fr and time t fa The details are as described above.

[0211] Next, the photosensitive transfer material in the present invention will be described in detail.

[0212] [Photosensitive transfer material]

[0213] The photosensitive transfer material of the present invention comprises at least a temporary support and a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator disposed on the temporary support. The photosensitive transfer material of the present invention can also be configured to have a structure having other layers such as a thermoplastic resin layer, an intermediate layer and a protective film (hereinafter referred to as a cover film) as required.

[0214] (Temporary support)

[0215] The temporary support is a support that can be peeled off from the photosensitive transfer material. The temporary support can support at least the photosensitive resin layer.

[0216] The temporary support may have a single-layer structure or a multi-layer structure.

[0217] The layer structure of the temporary support with multilayer structure is not limited. The temporary support with multilayer structure can have a coating layer or a functional layer. As a temporary support with multilayer structure, for example, a temporary support with a substrate and a coating layer or a functional layer can be cited. The coating layer is a layer covering a part or all of the surface of any layer (such as a substrate). As a functional layer, for example, an adhesive layer (closed layer) and a hard coat layer can be cited. The coating layer can be a functional layer.

[0218] The temporary support preferably has light transmittance. The temporary support has light transmittance, so that the photosensitive resin layer can be exposed in a pattern through the temporary support (hereinafter referred to as pattern exposure). "Having light transmittance" means that the transmittance of the light of the wavelength used in the pattern exposure is 50% or more. As the light transmittance of the temporary support, from the viewpoint of improving the exposure sensitivity of the photosensitive resin layer, the transmittance of the light of the wavelength (preferably 365nm) used in the pattern exposure is preferably 60% or more, more preferably 70% or more.

[0219] “Transmittance” is the ratio of the intensity of light emitted through the layer to be measured to the intensity of light incident in a direction perpendicular to the main surface of the layer to be measured (i.e., thickness direction). Transmittance is measured using MCPD Series manufactured by OTSUKA ELECTRONICS Co., LTD.

[0220] Examples of the temporary support include a glass substrate, a resin film, and paper. From the viewpoint of strength, flexibility, and light transmittance, a resin film is preferred.

[0221] Examples of the resin film include polyethylene terephthalate (PET) film, triacetyl cellulose (TAC) film, polystyrene (PS) film, and polycarbonate (PC) film, etc. Among them, a PET film is preferred, and a biaxially stretched PET film stretched in two directions of the X and Y axes is more preferred.

[0222] The thickness of the temporary support is not particularly limited. It can be selected according to the material from the viewpoints of improving the strength of the support, the flexibility required when laminating with the transferred substrate, and the resolution of the pattern formed by exposure of the photosensitive resin layer of the temporary support. The thickness of the temporary support is preferably in the range of 5 μm to 100 μm, more preferably in the range of 10 μm to 50 μm, and further preferably in the range of 10 μm to 30 μm from the perspective of ease of operation and versatility.

[0223] The average thickness of the temporary support is measured by the following method.

[0224] Use scanning electron microscope (SEM) to observe the cross section in the direction perpendicular to the main surface of the temporary support (i.e., thickness direction). According to the observed image obtained, the thickness of the temporary support at 10 points is measured. By arithmetic averaging the measured values, the average thickness of the temporary support is obtained. In addition, the measuring method is not limited to the temporary support with a single-layer structure, but is also applicable to the temporary support with a multilayer structure.

[0225] The temporary support preferably has deformation such as wrinkles, scratches, defects, and the like.

[0226] From the viewpoint of pattern formation when pattern exposure of the photosensitive resin layer is performed via a temporary support and the transparency of the temporary support, it is preferred that the number of particles, impurities, defects, precipitates, etc. contained in the temporary support is small. The number of particles, impurities, and defects with a diameter of 1 μm or more is preferably 50 / 10 mm. 2 Below, more preferably 10 / 10mm 2 Below, more preferably 3 / 10mm 2 Below, especially preferably 0 / 10mm 2 .

[0227] Preferred methods of temporary support bodies are described, for example, in paragraphs 0017 to 0018 of Japanese Patent Gazette No. 2014-85643, paragraphs 0019 to 0026 of Japanese Patent Gazette No. 2016-27363, paragraphs 0041 to 0057 of International Publication No. 2012 / 081680 A1, paragraphs 0029 to 0040 of International Publication No. 2018 / 179370 A1, and paragraphs 0012 to 0032 of Japanese Patent Gazette No. 2019-101405, and the contents of these gazettes are incorporated into this specification.

[0228] (Photosensitive resin layer)

[0229] The photosensitive resin layer contains an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator. The photosensitive resin layer can be configured as a negative photosensitive layer in which the solubility in the developer of the exposed exposed area (exposed portion) is reduced and the unexposed non-exposed area (non-exposed portion) is removed by development.

[0230] Furthermore, the photosensitive resin layer may further contain arbitrary components such as a pigment and a surfactant as necessary.

[0231] The photosensitive resin layer may be laminated directly on the temporary support or may be laminated via an arbitrary layer. In the photosensitive transfer material according to the present invention, an arbitrary layer may be laminated on the photosensitive resin layer.

[0232] The photosensitive resin layer preferably contains 10 to 90% by mass of an alkali-soluble resin, 5 to 70% by mass of a polymerizable compound, and 0.01 to 20% by mass of a photopolymerization initiator based on the total solid content (based on mass) of the photosensitive resin layer.

[0233] -Alkali soluble resin-

[0234] The photosensitive resin layer contains at least one kind of alkali-soluble resin (hereinafter, also referred to as polymer A). The alkali-soluble resin includes a polymer that is easily soluble in an alkali substance.

[0235] The acid value of polymer A can control the swelling of the photosensitive resin layer caused by acrylic acid solution (for example, alkaline developer during development, alkaline stripping solution during stripping, etc.). By controlling the acid value, it can be set to excellent resolution. As the acid value of polymer A, for the above reasons, it is preferably 220 mgKOH / g or less, more preferably less than 200 mgKOH / g, and further preferably less than 190 mgKOH / g. The lower limit of the acid value of polymer A is not particularly limited, preferably 60 mgKOH / g or more, more preferably 120 mgKOH / g or more, further preferably 150 mgKOH / g or more, and particularly preferably 170 mgKOH / g or more.

[0236] The acid value is the mass [mg] of potassium hydroxide required to neutralize 1 g of a sample, and is expressed in "mgKOH / g." The acid value can be calculated from the average content of acid groups in the compound, for example.

[0237] The acid value of the polymer A can be adjusted by the type of the structural unit constituting the polymer A and the content of the structural unit containing an acid group.

[0238] The weight average molecular weight of polymer A is preferably 5,000 to 500,000. If the weight average molecular weight is 500,000 or less, the resolution and developability can be improved. From this viewpoint, the weight average molecular weight is more preferably 100,000 or less, further preferably 60,000 or less, and particularly preferably 50,000 or less. Furthermore, if the weight average molecular weight is 5,000 or more, the hardness of the peeling sheet peeled off during peeling can be increased and the peeling sheet adhesion can be improved. Furthermore, from the viewpoint of controlling the properties of the developed agglomerate, the edge fusing property and the cutting property, the weight average molecular weight is preferably 5,000 or more. The weight average molecular weight is more preferably 10,000 or more, further preferably 20,000 or more, and particularly preferably 30,000 or more. The edge fusing property refers to the degree to which the photosensitive resin layer easily protrudes from the end surface of the roller when the photosensitive transfer material is wound into a roll. The cutting property refers to the degree to which the chips easily fly when the unexposed film is cut with a dicing machine. For example, if a chip adheres to the surface of a photosensitive transfer material, the chip is transferred to a mask during an exposure process, which may cause defective products.

[0239] The dispersity of polymer A is preferably 1.0 to 6.0, more preferably 1.0 to 5.0, further preferably 1.0 to 4.0, further preferably 1.0 to 3.0. The dispersity is the ratio of the weight average molecular weight to the number average molecular weight (weight average molecular weight / number average molecular weight). The weight average molecular weight and the number average molecular weight are values ​​measured using gel permeation chromatography.

[0240] From the viewpoint of suppressing the deterioration of line width thickness and resolution when the focus position is shifted during exposure, polymer A preferably contains constituent units derived from monomers having aromatic hydrocarbon groups. As aromatic hydrocarbon groups, for example, substituted or unsubstituted phenyl groups, substituted or unsubstituted aralkyl groups can be cited. The content ratio of constituent units derived from monomers having aromatic hydrocarbon groups in polymer A is preferably 20% by mass or more, more preferably 30% by mass or more, further preferably 40% by mass or more, particularly preferably 45% by mass or more, and most preferably 50% by mass or more, based on the total mass of the total constituent units. There is no particular limitation on the upper limit of the content ratio of constituent units derived from monomers having aromatic hydrocarbon groups, but it is preferably 95% by mass or less, and more preferably 85% by mass or less. In addition, in the case of containing multiple polymers A, the content ratio of constituent units derived from monomers having aromatic hydrocarbon groups is calculated as a mass average.

[0241] Examples of monomers having an aromatic hydrocarbon group include monomers having an aralkyl group, styrene, and polymerizable styrene derivatives (e.g., methylstyrene, vinyltoluene, tert-butoxystyrene, acetoxystyrene, 4-vinylbenzoic acid, styrene dimer, styrene trimer, etc.). Among them, monomers having an aralkyl group or styrene are preferred.

[0242] Examples of the aralkyl group include substituted or unsubstituted phenylalkyl (excluding benzyl) and substituted or unsubstituted benzyl. Among them, substituted or unsubstituted benzyl is preferred.

[0243] Examples of the monomer having a phenylalkyl group include phenylethyl (meth)acrylate and the like.

[0244] The polymer A may be a form in which the constituent units derived from the monomer having an aromatic hydrocarbon group include constituent units derived from styrene. The content ratio of the constituent units derived from styrene is based on the total mass of the total constituent units, preferably 20% to 50% by mass, more preferably 25% to 45% by mass, further preferably 30% to 40% by mass, and particularly preferably 30% to 35% by mass.

[0245] Examples of the monomer having a benzyl group include (meth)acrylates having a benzyl group (e.g., benzyl (meth)acrylate, benzyl (meth)acrylate chloride, etc.), vinyl monomers having a benzyl group (e.g., vinylbenzyl chloride, vinylbenzyl alcohol, etc.), etc. Among them, benzyl (meth)acrylate is preferred.

[0246] The polymer A may be in a form that contains a constituent unit derived from benzyl (meth)acrylate as a constituent unit derived from a monomer having an aromatic hydrocarbon group. The content ratio of the constituent unit derived from benzyl (meth)acrylate is preferably 50% to 95% by mass, more preferably 60% to 90% by mass, further preferably 70% to 90% by mass, and particularly preferably 75% to 90% by mass, based on the total mass of the total constituent units.

[0247] The polymer A including a structural unit derived from a monomer having an aromatic hydrocarbon group is preferably obtained by polymerizing a monomer having an aromatic hydrocarbon group and at least one of the first monomers described below and / or at least one of the second monomers described below.

[0248] The polymer A that does not contain a constituent unit derived from a monomer having an aromatic hydrocarbon group is preferably obtained by polymerizing at least one of the first monomers described later (excluding monomers having an aromatic hydrocarbon group), and is more preferably obtained by copolymerizing at least one of the first monomers (excluding monomers having an aromatic hydrocarbon group) with at least one of the second monomers described later (excluding monomers having an aromatic hydrocarbon group).

[0249] The first monomer is a monomer having a carboxyl group and a polymerizable unsaturated group in the molecule. The first monomer may be a monomer having no aromatic hydrocarbon group in the molecule. As the first monomer, for example, (meth) acrylic acid, fumaric acid, cinnamic acid, crotonic acid, itaconic acid, 4-vinylbenzoic acid, maleic anhydride, maleic acid half ester, etc. may be cited. Among these, (meth) acrylic acid is preferred.

[0250] The content ratio of the structural unit derived from the first monomer in the polymer A is preferably 5 to 50% by mass, more preferably 10 to 40% by mass, and further preferably 15 to 30% by mass, based on the total mass of all structural units.

[0251] The copolymerization ratio of the first monomer is based on the total mass of the total constituent units of the copolymerization, and is preferably 10% to 50% by mass. If the copolymerization ratio is 10% by mass or more, good developability is expressed, which is preferred in terms of being able to control edge fusing properties, etc. As the copolymerization ratio of the first monomer, it is more preferably 15% by mass or more, and further preferably 20% by mass or more. If the copolymerization ratio of the first monomer is 50% by mass or less, the resolution of the pattern and the shape of the hem of the pattern become good, and the chemical resistance of the pattern is also improved. As the copolymerization ratio of the first monomer, it is more preferably 35% by mass or less, further preferably 30% by mass or less, and particularly preferably 27% by mass or less.

[0252] The second monomer is a non-acidic monomer having at least one polymerizable unsaturated group in the molecule. Examples of the second monomer include (meth)acrylate esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, cyclohexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; esters of vinyl alcohol such as vinyl acetate; and (meth)acrylonitrile.

[0253] Among them, methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and n-butyl (meth)acrylate are preferred, and methyl (meth)acrylate is more preferred.

[0254] The content ratio of the structural unit derived from the second monomer in the polymer A is preferably 5 to 60 mass %, more preferably 15 to 50 mass %, and further preferably 20 to 45 mass %, based on the total mass of all structural units.

[0255] The polymer A preferably contains a structural unit derived from a monomer having an aralkyl group and / or a structural unit derived from styrene. This can suppress deterioration in line width and resolution when a focus position shift occurs during exposure.

[0256] Preferred examples of the polymer A include copolymers obtained by copolymerizing methacrylic acid, benzyl methacrylate, and styrene, and copolymers obtained by copolymerizing methacrylic acid, methyl methacrylate, benzyl methacrylate, and styrene.

[0257] As one embodiment of the polymer A, a polymer comprising 25 to 40% by mass of a constituent unit derived from a monomer having an aromatic hydrocarbon group, 20 to 35% by mass of a constituent unit derived from a first monomer, and 30 to 45% by mass of a constituent unit derived from a second monomer is a preferred embodiment. Furthermore, as another embodiment of the polymer A, a polymer comprising 70 to 90% by mass of a constituent unit derived from a monomer having an aromatic hydrocarbon group and 10 to 25% by mass of a constituent unit derived from a first monomer is a preferred embodiment.

[0258] The polymer A may be contained alone or in combination of two or more.

[0259] When two or more polymers A are mixed, it is preferred to mix two polymers A containing constituent units derived from a monomer having an aromatic hydrocarbon group or to mix a polymer A containing constituent units derived from a monomer having an aromatic hydrocarbon group and a polymer A containing no constituent units derived from a monomer having an aromatic hydrocarbon group. In the latter case, the content ratio of the polymer A containing constituent units derived from a monomer having an aromatic hydrocarbon group relative to the total constituent units of the polymer A is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0260] The polymer (A) may have any of a linear structure, a branched structure, and an alicyclic structure in a side chain.

[0261] By using a monomer containing a group having a branched structure on the side chain or a monomer containing a group having an alicyclic structure on the side chain, a branched structure, an alicyclic structure, or a branched structure and an alicyclic structure can be introduced into the side chain of the polymer (A). The group having an alicyclic structure may be monocyclic or polycyclic.

[0262] Specific examples of the monomer containing a group having a branched structure on the side chain include isopropyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, tert-amyl (meth)acrylate, sec-isoamyl (meth)acrylate, 2-octyl (meth)acrylate, 3-octyl (meth)acrylate, tert-octyl (meth)acrylate, etc. Among these, isopropyl (meth)acrylate, isobutyl (meth)acrylate, and tert-butyl methacrylate are preferred, and isopropyl methacrylate and tert-butyl methacrylate are more preferred.

[0263] Specific examples of the monomer containing a group having an alicyclic structure in the side chain include (meth)acrylates having an alicyclic hydrocarbon group having 5 to 20 carbon atoms. More specific examples include (bicyclo[2.2.1]hept-2)(meth)acrylate, 1-adamantyl(meth)acrylate, 2-adamantyl(meth)acrylate, 3-methyl-1-adamantyl(meth)acrylate, 3,5-dimethyl-1-adamantyl(meth)acrylate, 3-ethyladamantyl(meth)acrylate, 3-methyl-5-ethyl-1-adamantyl(meth)acrylate, 3,5,8-triethyl-1-adamantyl(meth)acrylate, 3,5-dimethyl-8-ethyl-1-adamantyl(meth)acrylate, 2-methyl-2-adamantyl(meth)acrylate, 2-ethyl-1-adamantyl(meth)acrylate, methyl (meth)acrylate, 2-hydroxy-2-adamantyl (meth)acrylate, 3-hydroxy-1-adamantyl (meth)acrylate, octahydro-4,7-benzyl-5-yl (meth)acrylate, octahydro-4,7-benzyl-1-ylmethyl (meth)acrylate, 1-menthol (meth)acrylate, tricyclodecane (meth)acrylate, 3-hydroxy-2,6,6-trimethyl-bicyclo〔3.1.1〕heptyl (meth)acrylate, 3,7,7-trimethyl-4-hydroxy-bicyclo〔4.1.0〕heptyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, fenchyl (meth)acrylate, 2,2,5-trimethylcyclohexyl (meth)acrylate, cyclohexyl (meth)acrylate, and the like. Among these (meth)acrylates, cyclohexyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, fenchyl (meth)acrylate, 1-menthol (meth)acrylate, and tricyclodecane (meth)acrylate are preferred, and cyclohexyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, 2-adamantyl (meth)acrylate, and tricyclodecane (meth)acrylate are more preferred.

[0264] The synthesis of polymer A is preferably carried out as follows: a free radical polymerization initiator such as benzoyl peroxide or azoisobutyronitrile is added in an appropriate amount to a solution of the above-mentioned single or multiple monomers diluted with a solvent such as acetone, methyl ethyl ketone, isopropanol, etc., and heated and stirred. Sometimes, a part of the mixture is added dropwise to the reaction solution while the synthesis is carried out. Sometimes, after the reaction is completed, a solvent is further added to adjust the concentration to the desired concentration. As a synthesis device, in addition to solution polymerization, bulk polymerization, suspension polymerization or emulsion polymerization can also be used.

[0265] The glass transition temperature (Tg) of the polymer A is preferably in the range of 30°C or higher and 135°C or lower.

[0266] If the Tg of polymer A is below 135°C, it is possible to suppress the deterioration of line width and resolution when the focus position shifts when exposing the photosensitive resin layer. From this viewpoint, the Tg of polymer A is more preferably below 130°C, further preferably below 120°C, and particularly preferably below 110°C. Furthermore, if the Tg of polymer A is above 30°C, the edge melting resistance can be improved. From this viewpoint, the Tg of polymer A is more preferably above 40°C, further preferably above 50°C, particularly preferably above 60°C, and most preferably above 70°C.

[0267] The content of polymer A in the photosensitive resin layer is preferably in the range of 10% to 90% by mass, more preferably 30% to 70% by mass, and further preferably 40% to 60% by mass, relative to the total solid content of the photosensitive resin layer. If the content of polymer A is 90% by mass or less, it is easy to control the development time. In addition, if the content of polymer A is 10% by mass or more, the edge fusing resistance can be improved.

[0268] -Polymerizable compounds-

[0269] The photosensitive resin layer contains at least one kind of polymerizable compounds.

[0270] The polymerizable compound is a compound that polymerizes under the action of a polymerization initiator described later, and is a compound different from the polymer A described above.

[0271] The polymerizable group of the polymerizable compound is not particularly limited as long as it is a group that contributes to the polymerization reaction, and examples thereof include groups having ethylenically unsaturated groups such as vinyl, acryloyl, methacryloyl, styryl, and maleimide groups; and groups having cationic polymerizable groups such as epoxy and oxetane groups. As the polymerizable group, a group having an ethylenically unsaturated group is preferred, and an acryloyl or methacryloyl group is more preferred.

[0272] --Polymerizable compound B--

[0273] The photosensitive resin layer preferably contains a polymerizable compound B having an aromatic ring and two ethylenically unsaturated groups. The polymerizable compound B is a bifunctional polymerizable compound having one or more aromatic rings in one molecule among the above-mentioned polymerizable compounds.

[0274] From the perspective of better resolution, the content of the polymerizable compound B in the photosensitive resin layer relative to the total amount of the polymerizable compound is preferably 40% by mass or more, more preferably 50% by mass or more, further preferably 55% by mass or more, and particularly preferably 60% by mass or more. The upper limit of the content of the polymerizable compound B is not particularly limited, but from the perspective of peelability, it is preferably 99% by mass or less, more preferably 95% by mass or less, further preferably 90% by mass or less, and particularly preferably 85% by mass or less.

[0275] As the aromatic ring contained in the polymerizable compound B, for example, there can be mentioned aromatic hydrocarbon rings such as a benzene ring, a naphthalene ring and an anthracene ring; aromatic heterocyclic rings such as a thiophene ring, a furan ring, a pyrrole ring, an imidazole ring, a triazole ring and a pyridine ring, and condensed rings thereof. As the aromatic ring, an aromatic hydrocarbon ring is preferred, and a benzene ring is more preferred. In addition, the aromatic ring may have a substituent.

[0276] The polymerizable compound B may be a compound having one aromatic ring or a compound having two or more aromatic rings.

[0277] The polymerizable compound B preferably has a bisphenol structure. When the polymerizable compound B has a bisphenol structure, swelling of the photosensitive resin layer caused by a developer during development can be suppressed, and as a result, the resolution can be improved.

[0278] Examples of the bisphenol structure include a bisphenol A structure derived from bisphenol A (2,2-bis(4-hydroxyphenyl)propane), a bisphenol F structure derived from bisphenol F (2,2-bis(4-hydroxyphenyl)methane), and a bisphenol B structure derived from bisphenol B (2,2-bis(4-hydroxyphenyl)butane), and a bisphenol A structure is preferred.

[0279] As the polymerizable compound B having a bisphenol structure, for example, there can be mentioned a compound having a bisphenol structure and two polymerizable groups (preferably (meth)acryloyl groups) bonded to both ends of the bisphenol structure. Both ends of the bisphenol structure may be directly bonded to the two polymerizable groups, or may be bonded through one or more alkyleneoxy groups. As the alkyleneoxy group, preferably ethyleneoxy or propyleneoxy, more preferably ethyleneoxy. In the case where the polymerizable group is bonded through an alkyleneoxy group, the number of alkyleneoxy groups attached to the bisphenol structure is preferably 4 to 16 per molecule, more preferably 6 to 14.

[0280] The polymerizable compound B having a bisphenol structure is described in paragraphs 0072 to 0080 of JP-A-2016-224162, and the contents described in the publication are incorporated into the present specification.

[0281] The polymerizable compound B is preferably a bifunctional ethylenically unsaturated compound having a bisphenol A structure, and more preferably 2,2-bis(4-((meth)acryloyloxypolyalkoxy)phenyl)propane.

[0282] Examples of 2,2-bis(4-((meth)acryloxypolyalkoxy)phenyl)propane include 2,2-bis(4-(methacryloxydiethoxy)phenyl)propane (e.g., FA-324M from Hitachi Chemical Co., Ltd.), 2,2-bis(4-(methacryloxyethoxypropoxy)phenyl)propane, 2,2-bis(4-(methacryloxypentaethoxy)phenyl)propane (e.g., BPE-200 and BPE-500 from Shin-Nakamura Chemical Co., Ltd.), 2,2-bis(4-(methacryloxydodecethoxytetrapropoxy)phenyl)propane (e.g., FA-3200MY from Hitachi Chemical Co., Ltd.), 2,2-bis(4-(methacryloxypentadecethoxy)phenyl)propane (e.g., Shin-Nakamura Chemical Co., Ltd.), and 2,2-bis(4-(methacryloxypentadecethoxy)phenyl)propane. Co., Ltd.'s BPE-1300), 2,2-bis(4-(methacryloyloxydiethoxy)phenyl)propane (e.g., BPE-200 from Shin-Nakamura Chemical Co., Ltd.) and ethoxylated (10) bisphenol A diacrylate (e.g., NK ESTER A-BPE-10 from Shin-Nakamura Chemical Co., Ltd.).

[0283] As the polymerizable compound B, preferably, a compound represented by the following formula (1) is used.

[0284] [Chemical formula 2]

[0285]

[0286] In formula (1), R 1 and R 2 Each independently represents a hydrogen atom or a methyl group, and A represents C 2 H 4 , B represents C 3 H 6 , n 1 and n 3 Each independently represents an integer from 1 to 39, and n1 +n 3 is an integer from 2 to 40, n 2 and n 4 Each independently represents an integer from 0 to 29, and n 2 +n 4 is an integer of 0 to 30. The arrangement of the repeating units of -(AO)- and -(BO)- may be random or block. When the arrangement is block, either -(AO)- or -(BO)- may be on the biphenyl side.

[0287] In one method, n 1 +n 2 +n 3 +n 4 It is preferably 2 to 40, and more preferably 2 to 35. 2 +n 4 It is preferably 0-10, and more preferably 0-4.

[0288] The polymerizable compound B may be used alone or in combination of two or more.

[0289] From the perspective of better resolution, the content of the polymerizable compound B in the photosensitive resin layer is preferably 10% by mass or more, and more preferably 20% by mass or more, relative to the solid content of the photosensitive resin layer. In addition, the upper limit of the content of the polymerizable compound B is not particularly limited, but from the perspective of transferability and edge (the phenomenon of photosensitive resin seeping from the end of the transfer member), it is preferably 70% by mass or less, and more preferably 60% by mass or less.

[0290] The photosensitive resin layer may contain a polymerizable compound other than the polymerizable compound B described above.

[0291] The polymerizable compounds other than the polymerizable compound B are not particularly limited and can be appropriately selected from known compounds, for example compounds having one ethylenically unsaturated group in one molecule (monofunctional ethylenically unsaturated compound), bifunctional ethylenically unsaturated compounds having no aromatic ring, and trifunctional or higher ethylenically unsaturated compounds.

[0292] Examples of the monofunctional ethylenically unsaturated compound include ethyl (meth)acrylate, ethylhexyl (meth)acrylate, 2-(meth)acryloyloxyethyl butanediol, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and phenoxyethyl (meth)acrylate.

[0293] Examples of the bifunctional ethylenically unsaturated compound having no aromatic ring include alkylene glycol di(meth)acrylate, polyalkylene glycol di(meth)acrylate, urethane di(meth)acrylate, and trimethylolpropane diacrylate.

[0294] Examples of the alkylene glycol di(meth)acrylate include tricyclodecane dimethanol diacrylate (e.g., NK ESTER A-DCP from Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol dimethacrylate (e.g., DCP from Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol diacrylate (e.g., A-NOD-N from Shin-Nakamura Chemical Co., Ltd.), 1,6-hexanediol diacrylate (e.g., A-HD-N from Shin-Nakamura Chemical Co., Ltd.), ethylene glycol dimethacrylate, 1,10-decanediol diacrylate, and neopentyl glycol di(meth)acrylate.

[0295] Examples of the polyalkylene glycol di(meth)acrylate include polyethylene glycol di(meth)acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, and polypropylene glycol di(meth)acrylate (eg, ARONIX M-270 manufactured by TOAGOSEI CO., LTD.).

[0296] Examples of urethane di(meth)acrylates include propylene oxide-modified urethane di(meth)acrylates and ethylene oxide- and propylene oxide-modified urethane di(meth)acrylates. Examples of commercially available urethane di(meth)acrylates include 8UX-015A (manufactured by TAISEI FINE CHEMICAL CO, LTD.), UA-32P (manufactured by Shin-Nakamura Chemicak Co., Ltd.), and UA-1100H (manufactured by Shin-Nakamura Chemicak Co., Ltd.).

[0297] Examples of trimethylolpropane diacrylate include NK ESTER A-TMPT manufactured by Shin-Nakamura Chemical Co., Ltd., and the like.

[0298] Examples of trifunctional or higher-functional ethylenically unsaturated compounds include dipentaerythritol (tri / tetra / penta / hexa) (meth)acrylate, pentaerythritol (tri / tetra) (meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, trimethylolethane tri(meth)acrylate, isocyanuric acid tri(meth)acrylate, glycerol tri(meth)acrylate, and alkylene oxide-modified products thereof.

[0299] Examples of the trimethylolpropane tri(meth)acrylate include ethoxylated trimethylolpropane tri(meth)acrylate, and examples of commercially available products include Arkema's Sartomer series (eg, Sartomer SR-454, Sartomer SR-502, etc.).

[0300] Examples of the isocyanuric acid tri(meth)acrylate include ethoxylated isocyanuric acid tri(meth)acrylate and ε-caprolactone-modified tri-(2-acryloyloxyethyl)isocyanurate. Examples of commercially available products include A-9300-1CL manufactured by Shin-Nakamura Chemical Co., Ltd.

[0301] Examples of the alkylene oxide-modified products of trifunctional or higher ethylenic unsaturated compounds include caprolactone-modified (meth)acrylate compounds (KAYARAD (registered trademark) DPCA-20 manufactured by Nippon Kayaku Co., Ltd., A-9300-1CL manufactured by Shin-Nakamura Chemical Co., Ltd., etc.), alkylene oxide-modified (meth)acrylate compounds (KAYARAD RP-1040 manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300 manufactured by Shin-Nakamura Chemical Co., Ltd., EBECRYL (registered trademark) 135 manufactured by DAICEL-ALLNEX LTD., etc.), ethoxylated glyceryl triacrylate (A-GLY-9E manufactured by Shin-Nakamura Chemical Co., Ltd., etc.), KAYARAD DPHA (manufactured by Nippon Kayaku Co., Ltd.), KAYARAD DPEA-12 (manufactured by Nippon Kayaku Co., Ltd.), ARONIX (registered trademark) TO-2349 (manufactured by TOAGOSEI CO., Ltd.), ARONIXM-520 (manufactured by TOAGOSEI CO., Ltd.), ARONIXM-510 (manufactured by TOAGOSEI CO., Ltd.), etc.

[0302] As polymerizable compounds other than the polymerizable compound B, polymerizable compounds having an acid group described in paragraphs 0025 to 0030 of JP-A-2004-239942 may be used.

[0303] The weight average molecular weight (Mw) of the polymerizable compound including the polymerizable compound B is preferably 200 to 3,000, more preferably 280 to 2,200, and even more preferably 300 to 2,200.

[0304] As one embodiment, the photosensitive resin layer preferably contains the above-mentioned polymerizable compound B and a trifunctional or higher ethylenically unsaturated compound as a polymerizable compound, and more preferably contains the above-mentioned polymerizable compound B and two or more trifunctional or higher ethylenically unsaturated compounds. In this case, the mass ratio of the polymerizable compound B to the trifunctional or higher ethylenically unsaturated compound (total mass of the polymerizable compound B: total mass of the trifunctional or higher ethylenically unsaturated compound) is preferably 1:1 to 5:1, more preferably 1.2:1 to 4:1, and further preferably 1.5:1 to 3:1.

[0305] The photosensitive resin layer preferably contains the above-mentioned polymerizable compound B and two or more trifunctional ethylenically unsaturated compounds as polymerizable compounds.

[0306] From the viewpoint of achieving a better balance between the photosensitivity and resolution of the photosensitive resin layer and the peelability during peeling, the photosensitive resin layer in the present invention preferably contains a compound having two or more functional groups (ethylenically unsaturated compounds) in one molecule. In addition, the photosensitive resin layer in the present invention adjusts the hardening portion (i.e., resin pattern) formed by exposing the photosensitive resin layer to a hardness suitable for peelability. From the viewpoint of further reducing the adhesion of the peeling sheet in the device generated by peeling of the cured portion, as a polymerizable compound, it is preferred to contain at least one of a difunctional ethylenically unsaturated compound having two ethylenically unsaturated groups in one molecule and a trifunctional ethylenically unsaturated compound having three ethylenically unsaturated groups in one molecule, and more preferably contains a difunctional ethylenically unsaturated compound and a trifunctional ethylenically unsaturated compound.

[0307] From the perspective of excellent peelability, the content of the bifunctional ethylenically unsaturated compound relative to the total amount of the polymerizable compound in the photosensitive resin layer is preferably 60% by mass or more, and may exceed 70% by mass. The upper limit of the content of the bifunctional ethylenically unsaturated compound is not particularly limited, and may be 100% by mass, but from the perspective of peeling sheet adhesion, it is preferably 70% by mass or less.

[0308] Furthermore, as the ethylenically unsaturated compound, a (meth)acrylate compound containing a (meth)acryloyl group as a polymerizable group is preferred.

[0309] In the first, second and third embodiments of the present invention, the photosensitive resin layer is adjusted to a hardness suitable for peelability by exposing the cured portion (resin pattern) formed by the photosensitive resin layer. From the viewpoint of further reducing the adhesion of the peeling piece in the device generated by the peeling of the cured portion, the photosensitive resin layer contains a difunctional ethylenically unsaturated compound and a trifunctional ethylenically unsaturated compound, and the content ratio of the trifunctional ethylenically unsaturated compound relative to the total amount of the polymerizable compound in the photosensitive resin layer is preferably 10% by mass or more, more preferably 30% by mass or more, and further preferably 40% by mass or more. In addition, for the same reasons as above, the content ratio of the trifunctional ethylenically unsaturated compound relative to the total amount of the polymerizable compound is preferably 70% by mass or less, more preferably 60% by mass or less, and further preferably 50% by mass or less.

[0310] In addition, for the same reasons as above, the thickness of the photosensitive resin layer is 5 μm or more and the content ratio of the trifunctional ethylenically unsaturated compound in the photosensitive resin layer relative to the total amount of the polymerizable compound is preferably 30 mass % to 70 mass %, and the thickness of the photosensitive resin layer is 10 μm or more and the content ratio of the trifunctional ethylenically unsaturated compound in the photosensitive resin layer relative to the total amount of the polymerizable compound is preferably 40 mass % to 70 mass %.

[0311] The polymerizable compound may be used alone or in combination of two or more.

[0312] The total amount of the polymerizable compound in the photosensitive resin layer is preferably 10 to 70% by mass, more preferably 20 to 60% by mass, and further preferably 20 to 50% by mass, based on the total solid content of the photosensitive resin layer.

[0313] -Photopolymerization initiator-

[0314] The photosensitive resin layer contains at least one kind of photopolymerization initiator.

[0315] The photopolymerization initiator is a compound that starts polymerization of a polymerizable compound under active light such as ultraviolet rays, visible rays, and X-rays. There are no particular limitations on the photopolymerization initiator, and a known photopolymerization initiator can be used.

[0316] Examples of the photopolymerization initiator include a photoradical polymerization initiator and a photocationic polymerization initiator, and a photoradical polymerization initiator is preferred.

[0317] Examples of the photoradical polymerization initiator include a photopolymerization initiator having an oxime ester structure, a photopolymerization initiator having an α-aminoalkylphenone structure, a photopolymerization initiator having an α-hydroxyalkylphenone structure, a photopolymerization initiator having an acylphosphine oxide structure, and a photopolymerization initiator having an N-phenylglycine structure.

[0318] As the photoradical polymerization initiator, it is preferred to contain at least one selected from 2,4,5-triarylimidazole dimers and derivatives thereof. This can further improve the photosensitivity, visibility of the exposed area and the non-exposed area, and resolution.

[0319] In addition, the two 2,4,5-triarylimidazole structures in the 2,4,5-triarylimidazole dimer and its derivatives may be the same or different.

[0320] Examples of the derivatives of 2,4,5-triarylimidazole dimers include 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, and 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer.

[0321] As the photoradical polymerization initiator, for example, polymerization initiators described in paragraphs 0031 to 0042 of JP-A-2011-95716 and paragraphs 0064 to 0081 of JP-A-2015-14783 can be used.

[0322] Examples of the photoradical polymerization initiator include ethyl dimethylaminobenzoate (DBE, CAS No. 10287-53-3), benzoin methyl ether, anisil (p,p'-dimethoxybenzyl), TAZ-110 (trade name: manufactured by Midori Kagaku Co., Ltd.), benzophenone, TAZ-111 (trade name: manufactured by Midori Kagaku Co., Ltd.), Irgacur EOXE01, OXE02, OXE03, OXE04 (manufactured by BASF), Omnirad 651 and 369 (trade name: manufactured by IGM Resins B.V.), and 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-bisimidazole (manufactured by Tokyo Chemical Industry Co., Ltd.).

[0323] Examples of commercially available photoradical polymerization initiators include 1-[4-(phenylthio)]-1,2-octanedione-2-(O-benzoyl oxime) (trade name: IRGACURE (registered trademark) OXE-01, manufactured by BASF), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyl oxime) (trade name: IRGACURE OXE-02, manufactured by BASF), IRGACURE OXE-03 (manufactured by BASF), IRGACURE OXE-04 (manufactured by BASF), 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnifad 379EG, IGM 379EG, manufactured by BASF), and 1-[(4-(4-morpholinyl)phenyl]-2-(dimethylamino)-1-[(4-(4-morpholinyl)phenyl]-2-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnifad 379EG, IGM 379EG). Resins B.V.), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (trade name: Omnirad 907, manufactured by IGM Resins B.V.), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one (trade name: Omnirad 127, manufactured by IGM Resins BV), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1 (trade name: Omnirad 369, manufactured by IGM Resins BV), 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Omnirad 1173, manufactured by IGM Resins BV), 1-hydroxycyclohexyl phenyl ketone (trade name: Omnirad 184, manufactured by IGM Resins BV), BV), 2,2-dimethoxy-1,2-diphenylethane-1-one (trade name: Omnirad 651, manufactured by IGM Resins B.V.), 2,4,6-trimethylbenzoyl-diphenylphosphine (trade name: Omnirad TPO H, manufactured by IGM Resins BV), bis(2,4,6-trimethylbenzoyl)phenylphosphine (trade name: Omnirad 819, manufactured by IGM Resins BV), oxime ester-based photopolymerization initiators (trade name: Lunar 6, manufactured by DKSH MANAGEMENT LTD.), 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenylbisimidazole (2-(2-chlorophenyl)-4,5-diphenylimidazole dimer) (trade name: B-CIM, manufactured by Hampford), and 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer (trade name: BCTB, manufactured by Tokyo Chemical Industry Co., Ltd.).

[0324] The photocationic polymerization initiator (ie, photoacid generator) is a compound that generates an acid under actinic rays.

[0325] As a photocationic polymerization initiator, there is no structural restriction, and preferably a compound that is responsive to actinic rays with a wavelength of more than 300nm (preferably a wavelength of 300-450nm) and generates acid. In addition, a photocationic polymerization initiator that is not directly responsive to actinic rays with a wavelength of more than 300nm can also be used as a compound that is responsive to actinic rays with a wavelength of more than 300nm and can generate acid by using a sensitizer. As a photocationic polymerization initiator, a photocationic polymerization initiator that generates acid with a pKa of less than 4 is preferred, a photocationic polymerization initiator that generates acid with a pKa of less than 3 is more preferred, and a photocationic polymerization initiator that generates acid with a pKa of less than 2 is particularly preferred. The lower limit of pKa is not particularly limited, and for example, it is preferably greater than -10.0.

[0326] Examples of the photocationic polymerization initiator include ionic photocationic polymerization initiators and nonionic photocationic polymerization initiators.

[0327] Examples of the ionic photocationic polymerization initiator include onium salt compounds such as diaryliodonium salts and triarylsulfonium salts, and quaternary ammonium salts. As the ionic photocationic polymerization initiator, the ionic photocationic polymerization initiators described in paragraphs 0114 to 0133 of JP-A-2014-85643 may also be used.

[0328] As nonionic photocationic polymerization initiators, for example, trichloromethyl-s-triazine compounds, diazomethane compounds, imidosulfonate compounds and oximesulfonate compounds can be cited. As trichloromethyl-s-triazine compounds, diazomethane compounds and imidosulfonate compounds, the compounds described in paragraphs 0083 to 0088 of Japanese Patent Publication No. 2011-221494 can be used. And, as oximesulfonate compounds, the compounds described in paragraphs 0084 to 0088 of International Publication No. 2018 / 179640 can be used.

[0329] The photosensitive resin layer preferably contains a photoradical polymerization initiator, and more preferably contains at least one selected from 2,4,5-triarylimidazole dimers and derivatives thereof.

[0330] The photosensitive resin layer may contain one photopolymerization initiator alone or two or more. The content of the photopolymerization initiator in the photosensitive resin layer is not particularly limited, and is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 1.0% by mass or more relative to the total solid content of the photosensitive resin layer. The upper limit of the content of the photopolymerization initiator is not particularly limited, and is preferably 10% by mass or less, and more preferably 5% by mass or less relative to the total solid content of the photosensitive resin layer.

[0331] -Optional ingredients-

[0332] The photosensitive resin layer may contain other components besides the above-mentioned alkali-soluble resin (polymer A), polymerizable compound, and photopolymerization initiator.

[0333] --pigment--

[0334] From the viewpoint of visibility of the exposed and non-exposed portions, visibility of the pattern after development, and resolution, the photosensitive resin layer preferably contains a pigment (also referred to as "pigment N") whose maximum absorption wavelength is 450 nm or more in the wavelength range of 400 nm to 780 nm when the color is developed and whose maximum absorption wavelength changes due to acid, alkali, or free radicals. If pigment N is contained, the detailed reason is unclear, but the adhesion with the adjacent layers (temporary support, intermediate layer, etc.) is improved, and the resolution is more excellent.

[0335] The "maximum absorption wavelength of a pigment changes due to acid, alkali or free radicals" means that a pigment in a colored state is decolorized by acid, alkali or free radicals, a pigment in a decolorized state is colored by acid, alkali or free radicals, and a pigment in a colored state is changed into a colored state of another hue.

[0336] Specifically, pigment N can be a compound that changes from a bleached state by exposure and develops color, or a compound that changes from a bleached state by exposure. In this case, it can be a pigment that changes in the state of developing or bleaching by acid, alkali or free radicals produced and worked in the photosensitive resin layer by exposure, or it can be a pigment that changes in the state (such as pH) in the photosensitive resin layer by acid, alkali or free radicals. And, it can also be a pigment that changes in the state of developing or bleaching by directly receiving acid, alkali or free radicals as stimulation without exposure.

[0337] Among them, from the viewpoint of visibility and resolution of the exposed and non-exposed areas, the dye N is preferably a dye whose maximum absorption wavelength is changed by an acid or a radical, and more preferably a dye whose maximum absorption wavelength is changed by a radical.

[0338] From the viewpoint of visibility and resolution of the exposed portion and the non-exposed portion, the photosensitive resin layer preferably contains, as the dye N, both a dye that changes the maximum absorption wavelength by radicals and a photoradical polymerization initiator.

[0339] Furthermore, from the viewpoint of visibility of the exposed portion and the non-exposed portion, the dye N is preferably a dye that develops color by acid, alkali, or radicals.

[0340] As an example of the coloring mechanism of the dye N, there can be cited a method in which a photoradical polymerization initiator, a photocationic polymerization initiator (photoacid generator) or a photobase generator is added to the photosensitive resin layer, and after exposure, free radicals, acid or base generated by the photoradical polymerization initiator, photocationic polymerization initiator or photobase generator develop free radical reactive dyes, acid reactive dyes or base reactive dyes (for example, colorless dyes).

[0341] From the viewpoint of visibility of the exposed and non-exposed areas, the maximum absorption wavelength of the dye N in the wavelength range of 400 nm to 780 nm during color development is preferably 550 nm or more, more preferably 550 nm to 700 nm, and even more preferably 550 nm to 650 nm.

[0342] Pigment N may have only one maximum absorption wavelength in the wavelength range of 400nm to 780nm when developing color, or may have two or more. When pigment N has two or more maximum absorption wavelengths in the wavelength range of 400nm to 780nm when developing color, the maximum absorption wavelength with the highest absorbance among the two or more maximum absorption wavelengths may be 450nm or more.

[0343] The maximum absorption wavelength of the dye N is determined by measuring the transmission spectrum of a solution containing the dye N (liquid temperature 25° C.) in the range of 400 nm to 780 nm using a spectrophotometer in an atmospheric environment and detecting the wavelength (maximum absorption wavelength) at which the intensity of light is minimal. For example, UV3100 manufactured by Shimadzu Corporation can be used as the spectrophotometer.

[0344] Examples of dyes that develop or fade color by exposure include colorless compounds.

[0345] Examples of the dye that is decolorized by exposure include colorless compounds, diarylmethane dyes, oxazine dyes, xanthene dyes, iminonaphthoquinone dyes, azomethine dyes, and anthraquinone dyes.

[0346] The dye N is preferably a colorless compound from the viewpoint of visibility of the exposed portion and the non-exposed portion.

[0347] Examples of the colorless compound include colorless compounds having a triarylmethane skeleton (triarylmethane-based pigments), colorless compounds having a spiropyran skeleton (spiropyran-based pigments), colorless compounds having a fluorane skeleton (fluorane-based pigments), colorless compounds having a diarylmethane skeleton (diarylmethane-based pigments), colorless compounds having a rhodamine lactam skeleton (rhodamine lactam-based pigments), colorless compounds having an indolylphthalide skeleton (indolylphthalide-based pigments), and colorless compounds having a colorless auronia skeleton (colorless auronia-based pigments).

[0348] Among them, triarylmethane-based dyes or fluoran-based dyes are preferred, and colorless compounds having a triphenylmethane skeleton (triphenylmethane-based dyes) or fluoran-based dyes are more preferred.

[0349] As a colorless compound, from the viewpoint of visibility of the exposed part and the non-exposed part, it is preferred to have a lactone ring, a Sudan ring or a sultone ring. Thus, by reacting the lactone ring, Sudan ring or sultone ring of the colorless compound with the free radical generated by the photo-free radical polymerization initiator or the acid generated by the photo-cationic polymerization initiator, the colorless compound can be changed to a closed-loop state to decolorize it or to an open-loop state to develop color. As a colorless compound, it is preferred to have a lactone ring, Sudan ring or sultone ring, and a compound that develops color by free radical or acid opening of the lactone ring, Sudan ring or sultone ring, and more preferably a compound that has a lactone ring and develops color by free radical or acid opening of the lactone ring.

[0350] Examples of the coloring matter N include the following dyes and colorless compounds.

[0351] Specific examples of the dye in the pigment N include brilliant green, ethyl violet, methyl green, crystal violet, Visin red, methyl violet 2B, quinolizine red, rose bengal, formyl yellow, thimorph, xylenol blue, methyl orange, p-methyl red, Congo red, benzopurine 4B, α-naphthyl red, naphthalene blue 2B, naphthalene blue A, methyl violet, malachite green, hydroquinone, Victoria pure blue-alkylnaphthalene sulfonate, Victoria pure blue BOH (manufactured by Hodogaya Chemical Co., Ltd.), Oil Blue #603 (manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.), Oil Pink #312 (manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.), Oil Red 5B (manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.), Oil Scarlet #308 (manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.), Oil Red OG (manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.), OilRed RR (manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.), Oil Green #502 (manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD.), Spiron Red BEH Special (manufactured by Hodogaya Chemical Co., Ltd.), m-cresol violet, cresol red, rhodamine B, rhodamine 6G, sulforhodamine B, golden ammonia, 4-p-diethylaminophenyliminonaphthoquinone, 2-carboxyanilino-4-p-diethylaminophenyliminonaphthoquinone, 2-carboxystearylamino-4-p-N,N-bis(hydroxyethyl)amino-phenyliminonaphthoquinone, 1-phenyl-3-methyl-4-p-diethylaminophenylimino-5-pyrazolone, and 1-β-naphthyl-4-p-diethylaminophenylimino-5-pyrazolone.

[0352] In the dye N, specific examples of the colorless compound include p,p',p"-hexamethyltriaminotriphenylmethane (colorless crystal violet), Pergascript Blue SRB (manufactured by Novartis International AG), crystal violet lactone, malachite green lactone, benzoyl leuco-methylene blue, 2-(N-phenyl-N-methylamino)-6-(N-p-tolyl-N-ethyl)aminofluoran, 2-anilino-3-methyl-6-(N-ethyl-p-formyldiamino)fluoran, 3,6-dimethoxyfluoran, 3-(N,N-diethylamino)-5-methyl-7-(N,N-dibenzylamino)fluoran, 3-(N-cyclohexyl-N-methylamino)- 6-methyl-7-anilinofluoran, 3-(N,N-diethylamino)-6-methyl-7-anilinofluoran, 3-(N,N-diethylamino)-6-methyl-7-phenylfluoran, 3-(N,N-diethylamino)-6-methyl-7-chlorofluoran, 3-(N,N-diethylamino)-6-methoxy-7-aminofluoran, 3-(N,N-diethylamino)-7-(4-chloroanilino)fluoran, 3-(N,N-diethylamino)-7-chlorofluoran, 3-( N, N-diethylamino)-7-benzylaminofluoran, 3-(N, N-diethylamino)-7,8-benzofluoran, 3-(N, N-dibutylamino)-6-methyl-7-anilinofluoran, 3-(N, N-dibutylamino)-6-methyl-7-phenylfluoran, 3-hydropyridyl-6-methyl-7-anilinofluoran, 3-pyrrolidino-6-methyl-7-anilinofluoran, 3,3-bis(1-ethyl-2-methylindol-3-yl)phthalide, 3,3-bis( 1-butyl-2-methylindol-3-yl)phthalide, 3,3-bis(p-dimethylaminophenyl)-6-dimethylaminophthalide, 3-(4-diethylamino-2-ethoxyphenyl)-3-(1-ethyl-2-methylindol-3-yl)-4-azaphthalide, 3-(4-diethylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)phthalide and 3',6'-bis(diphenylamino)spiroisobenzofuran-1(3H),9'-[9H]xan-3-one.

[0353] From the viewpoint of visibility of the exposed and non-exposed areas, and pattern visibility and resolution after development, the dye N is preferably a dye that changes the maximum absorption wavelength by radicals, and more preferably a dye that develops color by radicals.

[0354] As the pigment N, leuco crystal violet, crystal violet lactone, brilliant green or Victoria pure blue-alkylnaphthalene sulfonate is preferred.

[0355] The dye N may be used alone or in combination of two or more.

[0356] From the viewpoint of visibility of the exposed and non-exposed portions, and visibility and resolution of the pattern after development, the content of the pigment N is preferably 0.1% by mass or more, more preferably 0.1% by mass to 10% by mass, further preferably 0.1% by mass to 5% by mass, and particularly preferably 0.1% by mass to 1% by mass, relative to the total solid content of the photosensitive resin layer.

[0357] The content of the dye N refers to the content of the dye when all of the dye N contained in the photosensitive resin layer is in a colored state.

[0358] The content of the pigment N was determined as follows.

[0359] Hereinafter, a method for quantifying the content of the dye N will be described by taking a dye that develops color by radicals as an example.

[0360] Specifically, the solution of 0.001g and 0.01g of pigment dissolved in 100mL (milliliter) of methyl ethyl ketone was prepared. The photoradical polymerization initiator Irgacure OXE01 (trade name, BASF JAPAN LTD.) was added to each solution obtained, and the light of 365nm was irradiated to generate free radicals, so that all pigments became color-developing state. Afterwards, under the atmospheric environment, the absorbance of each solution under the condition of 25°C was measured using a spectrophotometer (UV3100, Shimadzu Corporation), and a calibration curve was made. Then, instead of the pigment, 3g of the photosensitive resin layer was dissolved in methyl ethyl ketone. In addition, the absorbance of the solution that made the pigments all color-developing was measured by the same method as above. From the absorbance of the solution containing the obtained photosensitive resin layer, the content of the pigment contained in the photosensitive resin layer was calculated according to the calibration curve.

[0361] --Surfactant--

[0362] From the viewpoint of thickness uniformity, the photosensitive resin layer preferably contains a surfactant.

[0363] Examples of the surfactant include anionic surfactants, cationic surfactants, nonionic (nonionic) surfactants, and amphoteric surfactants, and nonionic surfactants are preferred.

[0364] Examples of the nonionic surfactant include polyoxyethylene higher alkyl ether compounds, polyoxyethylene higher alkylphenyl ether compounds, higher fatty acid diester compounds of polyoxyethylene glycol, silicone nonionic surfactants, and fluorine nonionic surfactants.

[0365] From the aspect of better resolution, the photosensitive resin layer preferably contains a fluorine-based nonionic surfactant. By containing a fluorine-based nonionic surfactant in the photosensitive resin layer, the etching solution used in the etching process is inhibited from penetrating into the photosensitive resin layer, and sidewall etching can be reduced. As commercially available products of fluorine-based nonionic surfactants, for example, Megaface F-551, F-552 and F-554 (all made by DIC CORPORATION) can be cited.

[0366] In addition, as commercially available products of fluorine-based surfactants, for example, Megaface F-171, F-172, F-173, F-176, F-177, F-141, F-142, F-143, F-144, F-437, F-475, F-477, F-479, F-482, F-555-A, F-556, F-557, F-558, F-559, F-560, F-561, F-565, F-563, F-568, F-575, F-780, EXP, MFS-330, R-41, R-41-LM, R-01, R-40, R-40-LM, RS-43, TF-1956, RS-90, R-94, RS-72-K, DS-21 (all manufactured by DIC Corporation), Fluorad FC430, FC431, FC171 (all manufactured by Sumitomo 3M Limited), Surflon S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393, KH-40 (all manufactured by AGC Corporation), PolyFox PF636, PF656, PF6320, PF6520, PF7002 (all manufactured by OMNOVA SOLUTIONS INC.), Ftergent 710FL, 710FM, 610FM, 601AD, 601ADH2, 602A, 215M, 245F, 251, 212M, 250, 209F, 222F, 208G, 710LA, 710FS, 730LM, 650AC, 681, 683 (all manufactured by NEOS), etc. In addition, as a fluorine-based surfactant, an acrylic compound having a molecular structure having a functional group containing a fluorine atom and having a portion of the functional group containing a fluorine atom cut off and the fluorine atom volatilized when heat is applied can also be preferably used. As such a fluorine-based surfactant, the Megaface DS series manufactured by DIC CORPORATION (Chemical Industry Daily (February 22, 2016), Nikkei Industry News (February 23, 2016)), for example, Megaface DS-21, can be cited. Furthermore, as the fluorine-based surfactant, a polymer of a fluorine-containing vinyl ether compound having a fluorinated alkyl group or a fluorinated alkylene ether group and a hydrophilic vinyl ether compound is also preferably used.

[0367] Furthermore, a block polymer can also be used as the fluorine-based surfactant.

[0368] Furthermore, as the fluorine-based surfactant, a fluorine-containing polymer compound comprising a constituent unit derived from a (meth)acrylate compound having a fluorine atom and a constituent unit derived from a (meth)acrylate compound having 2 or more (preferably 5 or more) alkyleneoxy groups (preferably ethyleneoxy and propyleneoxy) can also be preferably used.

[0369] Furthermore, as the fluorine-based surfactant, a fluorine-containing polymer having a group containing an ethylenically unsaturated bond in a side chain may be used, such as Megaface RS-101, RS-102, RS-718K, RS-72-K (all manufactured by DIC CORPORATION).

[0370] From the viewpoint of improving environmental suitability, the fluorine-based surfactant is preferably a surfactant derived from an alternative material of a compound having a linear perfluoroalkyl group having 7 or more carbon atoms, such as perfluorooctane acid (PFOA) and perfluorooctane sulfonate (PFOS).

[0371] Examples of the nonionic surfactant include glycerin, trimethylolpropane, trimethylolethane, and ethoxylates and propoxylates thereof (e.g., glycerin propoxylate, glycerin ethoxylate, etc.), polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyethylene glycol dilaurate, polyethylene glycol distearate, sorbitan fatty acid esters, Pluronic (registered trademark) L10, L31, L61, L62, 10R5, 17R2, 25R2 (all manufactured by BASF), Tetronic 304, 701, 704, 901, 904, 150R1 (all manufactured by BASF), Solsperse 20000 (all manufactured by The Lubrizol Corporation), NCW-101, NCW-1001, NCW-1002 (all manufactured by FUJIFILM Wako Pure Chemical Corporation), PIONIN D-6112, D-6112-W, D-6315 (all manufactured by Takemoto Oil & Fat Co., Ltd.), OLFINE E1010, Surfynol 104, 400, 440 (all manufactured by Nissin Chemical Co., Ltd.), etc.

[0372] Examples of the silicone-based surfactant include linear polymers composed of siloxane bonds and modified siloxane polymers having an organic group introduced into a side chain or a terminal.

[0373] Specific examples of the surfactant include DOWSIL 8032 ADDITIVE, Toray SILICONE DC3PA, Toray SILICONE SH7PA, Toray SILICONE DC11PA, Toray SILICONE SH21PA, Toray SILICONE SH28PA, Toray SILICONE SH29PA, Toray SILICONE SH30PA, and Toray SILICONE SH8400 (all of which are Dow Corning Toray Co., Ltd.) and X-22-4952, X-22-4272, X-22-6266, KF-351A, K354L, KF-355A, KF-945, KF-640, KF-642, KF-643, X-22-6191, X-22-4515, KF-6004, KP-341, KF-6001, KF-6002 (all manufactured by Shin-Etsu Silicone Co., Ltd.), F-4440, TSF-4300, TSF-4445, TSF-4460, TSF-4452 (all manufactured by Momentive performance Materials Inc.), BYK307, BYK323, BYK330 (all manufactured by BYK Co., LTD), etc.

[0374] As the surfactant, the surfactant described in paragraphs 0120 to 0125 of International Publication No. 2018 / 179640, the surfactant described in paragraph 0017 of Japanese Patent No. 4502784, and the surfactant described in paragraphs 0060 to 0071 of Japanese Patent Application Laid-Open No. 2009-237362 can also be used.

[0375] The photosensitive resin layer may contain one surfactant alone or two or more surfactants. The content of the surfactant is preferably 0.001% to 10% by mass, more preferably 0.01% to 3% by mass, based on the total solid content of the photosensitive resin layer.

[0376] --additive--

[0377] The photosensitive resin layer may contain known additives in addition to the above-mentioned components as necessary.

[0378] Examples of the additive include polymerization inhibitors, sensitizers, plasticizers, heterocyclic compounds, benzotriazole compounds, carboxybenzotriazole compounds, resins other than polymer A, and solvents. The photosensitive resin layer may contain each additive alone or in combination of two or more.

[0379] The photosensitive resin layer may contain a polymerization inhibitor.

[0380] As the polymerization inhibitor, free radical polymerization inhibitors can be mentioned. As the free radical polymerization inhibitor, for example, the thermal polymerization inhibitor described in paragraph 0018 of Japanese Patent Gazette No. 4502784 can be mentioned. Among them, phenothiazine, phenoxazine or 4-methoxyphenol is preferred. As other free radical polymerization inhibitors, naphthylamine, cuprous chloride, nitrosophenylhydroxylamine aluminum salt, diphenylnitrosoamine, etc. can be mentioned. In order not to impair the sensitivity of the photosensitive resin composition, nitrosophenylhydroxylamine aluminum salt is preferably used as the free radical polymerization inhibitor.

[0381] Examples of the benzotriazole compound include 1,2,3-benzotriazole, 1-chloro-1,2,3-benzotriazole, bis(N-2-ethylhexyl)aminomethylene-1,2,3-benzotriazole, bis(N-2-ethylhexyl)aminomethylene-1,2,3-tolyltriazole, and bis(N-2-hydroxyethyl)aminomethylene-1,2,3-benzotriazole.

[0382] Examples of the carboxybenzotriazole compound include 4-carboxy-1,2,3-benzotriazole, 5-carboxy-1,2,3-benzotriazole, N-(N,N-di-2-ethylhexyl)aminomethylenecarboxybenzotriazole, N-(N,N-di-2-hydroxyethyl)aminomethylenecarboxybenzotriazole, and N-(N,N-di-2-ethylhexyl)aminovinylcarboxybenzotriazole. Examples of the carboxybenzotriazole include commercially available products such as CBT-1 (trade name of JOHOKU CHEMICAL CO., LTD).

[0383] The total content of the polymerization inhibitor, the benzotriazole compound, and the carboxybenzotriazole compound is preferably 0.01% to 3% by mass, and more preferably 0.05% to 1% by mass, relative to the total solid content of the photosensitive resin layer. If the total content is 0.01% by mass or more, the storage stability of the photosensitive resin layer becomes better. In addition, if the total content is 3% by mass or less, the sensitivity can be maintained and the decolorization of the dye can be effectively suppressed.

[0384] The photosensitive resin layer may contain a sensitizer.

[0385] The sensitizer is not particularly limited, and known sensitizers, dyes and pigments can be used. Examples of the sensitizer include dialkylaminobenzophenone compounds, pyrazoline compounds, anthracene compounds, coumarin compounds, xanthone compounds, thioxanthone compounds, acridone compounds, oxazole compounds, benzoxazole compounds, thiazole compounds, benzothiazole compounds, triazole compounds (e.g., 1,2,4-triazole), stilbene compounds, triazine compounds, thiophene compounds, naphthalimide compounds, triarylamine compounds and aminoacridine compounds.

[0386] The photosensitive resin layer may contain one type of sensitizer alone, or may contain two or more types.

[0387] When the photosensitive resin layer contains a sensitizer, the content of the sensitizer can be appropriately selected according to the purpose. From the viewpoint of improving the sensitivity to the light source and improving the curing speed based on the balance between the polymerization rate and the chain transfer, the content of the sensitizer is preferably 0.01% by mass to 5% by mass, and more preferably 0.05% by mass to 1% by mass, relative to the total mass of the photosensitive resin layer.

[0388] The photosensitive resin layer may contain at least one selected from a plasticizer and a heterocyclic compound. Examples of the plasticizer and the heterocyclic compound include compounds described in paragraphs 0097 to 0103 and paragraphs 0111 to 0118 of International Publication No. 2018 / 179640.

[0389] The photosensitive resin layer may contain a resin other than the polymer A.

[0390] The photosensitive resin layer may contain, for example, a resin in which the content ratio of the structural unit derived from styrene is 40% by mass or less relative to the total structural units.

[0391] Examples of resins other than polymer A include acrylic resins, styrene-acrylic copolymers (wherein the styrene content is 40% by mass or less), polyurethanes, polyvinyl alcohols, polyvinyl formals, polyamides, polyesters, polyamides, epoxy resins, polyacetals, polyhydroxystyrene, polyimides, polybenzoxazoles, polysiloxanes, polyethylene imines, polyallylamines, and polyalkylene glycols.

[0392] The photosensitive resin layer may contain a solvent.

[0393] When a photosensitive resin layer is formed using a photosensitive resin composition containing a solvent, the solvent may remain in the photosensitive resin layer.

[0394] The photosensitive resin layer may further contain known additives.

[0395] As known additives, metal oxide particles, antioxidants, dispersants, acid multipliers, development accelerators, conductive fibers, thermal free radical polymerization initiators, thermal acid generators, ultraviolet absorbers, thickeners, crosslinking agents, and organic or inorganic anti-precipitation agents can be cited. The additives contained in the photosensitive resin layer are described in paragraphs 0165 to 0184 of Japanese Patent Application Publication No. 2014-85643, and the contents described in the publication are incorporated into this specification.

[0396] (Impurities, etc.)

[0397] The photosensitive resin layer may contain a predetermined amount of impurities. Specific examples of impurities include sodium, potassium, magnesium, calcium, iron, manganese, copper, aluminum, titanium, chromium, cobalt, nickel, zinc, tin, halogens, and ions thereof. Among the above, halide ions, sodium ions, and potassium ions are easily mixed as impurities, so it is preferably set to the following content.

[0398] The content of impurities in the photosensitive resin layer is preferably 80 ppm or less, more preferably 10 ppm or less, and further preferably 2 ppm or less, based on mass. The content of impurities in the photosensitive resin layer can be 1 ppb or more or 0.1 ppm or more, based on mass.

[0399] To set the impurities within the above range, there are the following methods: selecting a raw material with a small impurity content as the raw material of the photosensitive resin layer, preventing the impurities from being mixed when forming the photosensitive resin layer, and cleaning the manufacturing equipment to remove the impurities. In this way, the impurity amount can be set within the above range.

[0400] Impurities can be quantified by a known method, for example, ICP (Inductively Coupled Plasma) emission spectrometry, atomic absorption spectrometry, or ion chromatography.

[0401] The content of benzene, formaldehyde, trichloroethylene, 1,3-butadiene, carbon tetrachloride, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide and hexane in the photosensitive resin layer is preferably small. The content of the above-mentioned compound in the photosensitive resin layer is preferably 100 ppm or less, more preferably 20 ppm or less, and further preferably 4 ppm or less, based on mass. The content of the above-mentioned compound in the photosensitive resin layer can be set to 10 ppb or more or 100 ppb or more based on mass. The above-mentioned compound can suppress the content by the same method as the impurities of the above-mentioned metal. And, it can be quantified by a known determination method.

[0402] The water content in the photosensitive resin layer is preferably 0.01% by mass to 1.0% by mass, and more preferably 0.05% by mass to 0.5% by mass, from the viewpoint of improving reliability and lamination properties.

[0403] ~Physical properties, etc.~

[0404] The thickness of the photosensitive resin layer is usually preferably 0.1μm to 300μm, more preferably 0.2μm to 100μm, further preferably 0.5μm to 50μm, and further preferably 0.5μm to 15μm. If the thickness of the photosensitive resin layer is within the above range, the developability of the photosensitive resin layer can be improved, and the resolution can be improved. In addition, the thickness of the photosensitive resin layer is adjusted to a hardness suitable for peelability of the cured portion (resin pattern) formed by exposing the photosensitive resin layer. From the perspective of further reducing the adhesion of the peeling sheet in the device generated by the peeling of the cured portion, it is preferably 1μm or more, more preferably 3μm or more, and further preferably 5μm or more. In addition, from the perspective of combining resolution, the thickness of the photosensitive resin layer is preferably 50μm or less, and more preferably 30μm or less.

[0405] The thickness of each layer in the photosensitive transfer material is determined by observing a cross section parallel to the direction perpendicular to the main surface of the photosensitive transfer material using a scanning electron microscope (SEM), measuring the thickness of each layer at 10 points based on the observed image, and calculating the average value thereof. The main surface of the photosensitive transfer material refers to two surfaces facing each other with a wider area than the other surfaces.

[0406] In terms of better adhesion, the transmittance of the photosensitive resin layer at a wavelength of 365 nm is preferably 10% or more, more preferably 30% or more, and further preferably 50% or more. The upper limit of the transmittance at a wavelength of 365 nm is not particularly limited and can be 99.9% or less.

[0407] ~Formation method~

[0408] The method for forming the photosensitive resin layer is not particularly limited as long as it is a method that can form a layer containing the above-mentioned components. As a method for forming the photosensitive resin layer, for example, there can be mentioned a method of forming by preparing a photosensitive resin composition containing an alkali-soluble resin, a polymerizable compound, a photopolymerization initiator and a solvent, applying the photosensitive resin composition to the surface of a temporary support, etc., and drying the coating film of the photosensitive resin composition.

[0409] Examples of the photosensitive resin composition used for forming the photosensitive resin layer include compositions containing an alkali-soluble resin, a polymerizable compound, a photopolymerization initiator, a solvent, and optional components. The photosensitive resin composition adjusts the viscosity of the photosensitive resin composition and preferably contains a solvent in order to facilitate formation of the photosensitive resin layer.

[0410] -Solvents-

[0411] As the solvent contained in the photosensitive resin composition, a known solvent that dissolves or disperses the alkali-soluble resin, the polymerizable compound, the photopolymerization initiator, the solvent, and the optional components can be used.

[0412] Examples of the solvent include alkylene glycol ether solvents, alkylene glycol ether acetate solvents, alcohol solvents (methanol, ethanol, etc.), ketone solvents (acetone, methyl ethyl ketone, etc.), aromatic hydrocarbon solvents (toluene, etc.), aprotic polar solvents (N,N-dimethylformamide, etc.), cyclic ether solvents (tetrahydrofuran, etc.), ester solvents, amide solvents, lactone solvents, and mixed solvents containing two or more of these.

[0413] When a photosensitive transfer material having a temporary support, a thermoplastic resin layer, an intermediate layer, and a photosensitive resin layer is produced, the photosensitive resin composition for forming the photosensitive resin layer preferably contains at least one selected from an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent. Among them, a mixed solvent containing at least one selected from an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent and at least one selected from a ketone solvent and a cyclic ether solvent is more preferred, and a mixed solvent containing at least three selected from an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent, a ketone solvent, and a cyclic ether solvent is further preferred.

[0414] Examples of the alkylene glycol ether solvent include ethylene glycol monoalkyl ether, ethylene glycol dialkyl ether, propylene glycol monoalkyl ether, propylene glycol dialkyl ether, diethylene glycol dialkyl ether, dipropylene glycol monoalkyl ether, and dipropylene glycol dialkyl ether.

[0415] Examples of the alkylene glycol ether acetate solvent include ethylene glycol monoalkyl ether acetate, propylene glycol monoalkyl ether acetate, diethylene glycol monoalkyl ether acetate, and dipropylene glycol monoalkyl ether acetate.

[0416] As the solvent, the solvents described in paragraphs 0092 to 0094 of International Publication No. 2018 / 179640 and the solvents described in paragraph 0014 of Japanese Patent Application Laid-Open No. 2018-177889 can be used, and these contents are incorporated into this specification.

[0417] The photosensitive resin composition may contain one type of solvent alone, or may contain two or more types.

[0418] The content of the solvent in the photosensitive resin composition is preferably 50% by mass to 1,900% by mass, and more preferably 100% by mass to 900% by mass, based on the total solid content of the photosensitive resin composition.

[0419] The preparation method of the photosensitive resin composition is not particularly limited, and an example of the method for preparing the photosensitive resin composition is as follows: a solution of each component dissolved in the above-mentioned solvent is prepared in advance, and the solution is mixed in a predetermined ratio. Before forming the photosensitive resin layer, the photosensitive resin composition is preferably filtered using a filter with a pore size of 0.2 μm to 30 μm.

[0420] The method for applying the photosensitive resin composition is not particularly limited, and the photosensitive resin composition may be applied by a known method.

[0421] Examples of the coating method include slit coating, spin coating, curtain coating, and inkjet coating.

[0422] The photosensitive resin composition is applied onto a cover film described later and dried to form a photosensitive resin layer on the cover film.

[0423] (Thermoplastic resin layer)

[0424] The photosensitive transfer material may have a thermoplastic resin layer between the temporary support and the photosensitive resin layer.

[0425] The photosensitive transfer material preferably has a thermoplastic resin layer between the temporary support and the photosensitive resin layer. The photosensitive transfer material has a thermoplastic resin layer between the temporary support and the photosensitive resin layer, so that the followability of the transferred substrate in the process of laminating the photosensitive transfer material to the transferred substrate (laminating process) is improved, and the mixing of bubbles between the transferred substrate and the photosensitive transfer material is suppressed. As a result, the adhesion with the adjacent layer (such as the temporary support) is improved.

[0426] -Alkali soluble resin-

[0427] The thermoplastic resin layer contains an alkali-soluble resin as the thermoplastic resin. The alkali-soluble resin in the thermoplastic resin layer may be the same as or different from the alkali-soluble resin in the photosensitive resin layer.

[0428] Examples of the alkali-soluble resin include acrylic resins, polystyrene resins, styrene-acrylic copolymers, polyurethane resins, polyvinyl alcohol, polyvinyl formal, polyamide resins, polyester resins, polyamide resins, epoxy resins, polyacetal resins, polyhydroxystyrene resins, polyimide resins, polybenzoxazole resins, polysiloxane resins, polyethyleneimine, polyallylamine, and polyalkylene glycol.

[0429] As the alkali-soluble resin, acrylic resin is preferred from the viewpoint of developability and adhesion to adjacent layers. The acrylic resin refers to a resin having at least one structural unit selected from structural units derived from (meth)acrylic acid, structural units derived from (meth)acrylates, and structural units derived from (meth)acrylic acid amides.

[0430] As the acrylic resin, the total content of the constituent units derived from (meth)acrylic acid, the constituent units derived from (meth)acrylic acid ester, and the constituent units derived from (meth)acrylic acid amide is preferably 50% by mass or more relative to the total mass of the acrylic resin. Among them, the total content of the constituent units derived from (meth)acrylic acid and the constituent units derived from (meth)acrylic acid ester is preferably 30% by mass to 100% by mass, and more preferably 50% by mass to 100% by mass relative to the total mass of the acrylic resin.

[0431] Furthermore, the alkali-soluble resin is preferably a polymer having an acid group.

[0432] Examples of the acid group include a carboxyl group, a sulfone group, a phosphoric acid group and a phosphonic acid group, and a carboxyl group is preferred.

[0433] From the viewpoint of developability, the alkali-soluble resin is more preferably an alkali-soluble resin having an acid value of 60 mgKOH / g or more, and is further preferably a carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more.

[0434] The upper limit of the acid value of the alkali-soluble resin is not particularly limited, but is preferably 200 mgKOH / g or less, and more preferably 150 mgKOH / g or less.

[0435] The carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more is not particularly limited, and any resin can be appropriately selected from known resins and used.

[0436] For example, the alkali-soluble resin of the carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more in the polymer described in paragraph 0025 of JP-A-2011-95716, the carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more in the polymer described in paragraphs 0033 to 0052 of JP-A-2010-237589, and the carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more in the binder polymer described in paragraphs 0053 to 0068 of JP-A-2016-224162.

[0437] The copolymerization ratio of the structural unit having a carboxyl group in the carboxyl group-containing acrylic resin is preferably 5 to 50% by mass, more preferably 10 to 40% by mass, and further preferably 12 to 30% by mass, based on the total mass of the acrylic resin.

[0438] As the alkali-soluble resin, an acrylic resin having a structural unit derived from (meth)acrylic acid is particularly preferred from the viewpoint of developability and adhesion to an adjacent layer.

[0439] The alkali-soluble resin may have a reactive group.

[0440] The reactive group may be any group capable of addition polymerization, and examples thereof include ethylenically unsaturated groups; polycondensable groups such as hydroxyl groups and carboxyl groups; and polyaddition reactive groups such as epoxy groups and (blocked) isocyanate groups.

[0441] The weight average molecular weight (Mw) of the alkali-soluble resin is preferably 1,000 or more, more preferably 10,000 to 100,000, and even more preferably 20,000 to 50,000.

[0442] The alkali-soluble resin may be used alone or in combination of two or more thereof. From the viewpoint of developability and adhesion to adjacent layers, the content of the alkali-soluble resin in the thermoplastic resin layer is preferably 10% to 99% by mass, more preferably 20% to 90% by mass, further preferably 40% to 80% by mass, and particularly preferably 50% to 70% by mass relative to the total mass of the thermoplastic resin layer.

[0443] -pigment-

[0444] The thermoplastic resin layer preferably contains a pigment (also referred to as "pigment B") having a maximum absorption wavelength of 450 nm or longer in the wavelength range of 400 nm to 780 nm when developing color and having a maximum absorption wavelength that is changed by acid, base or radical.

[0445] Preferred aspects of the dye B are the same as preferred aspects of the dye N except for the points described below.

[0446] Among them, from the viewpoint of visibility and resolution of the exposed and non-exposed areas, the dye B is preferably a dye whose maximum absorption wavelength is changed by an acid or a radical, and more preferably a dye whose maximum absorption wavelength is changed by an acid.

[0447] From the viewpoint of visibility and resolution of the exposed and non-exposed areas, the thermoplastic layer preferably contains, as the dye B, both a dye whose maximum absorption wavelength is changed by acid and a compound that generates acid by light, which will be described later.

[0448] The dye B may be used alone or in combination of two or more.

[0449] From the viewpoint of visibility of the exposed and non-exposed parts, the content of the pigment B is preferably 0.2% by mass or more, more preferably 0.2% by mass to 6% by mass, further preferably 0.2% by mass to 5% by mass, and particularly preferably 0.25% by mass to 3.0% by mass, relative to the total mass of the thermoplastic resin layer.

[0450] The content of the dye B refers to the content of the dye when all the dye B contained in the thermoplastic resin layer is in a colored state. Hereinafter, a quantitative method of the content of the dye B will be described using a dye that develops color by radicals as an example.

[0451] A solution was prepared by dissolving 0.001 g and 0.01 g of the pigment in 100 mL of methyl ethyl ketone. A photoradical polymerization initiator Irgacure OXE01 (trade name, BASF JAPAN LTD.) was added to each solution obtained, and irradiated with 365 nm light to generate free radicals, so that all the pigments became a color-developing state. Afterwards, a spectrophotometer (UV3100, made by Shimadzu Corporation) was used to measure the absorbance of each solution at a liquid temperature of 25° C. in an atmospheric environment, and a calibration curve was prepared.

[0452] Next, 0.1 g of the thermoplastic resin layer was dissolved in methyl ethyl ketone instead of the pigment, and the absorbance of the solution in which the pigment was completely colored was measured by the same method as above. From the absorbance of the solution containing the obtained thermoplastic resin layer, the amount of the pigment contained in the thermoplastic resin layer was calculated according to the calibration curve.

[0453] -Compounds that generate acids, bases or free radicals by light-

[0454] The thermoplastic resin layer may contain a compound that generates an acid, a base, or a radical by light (also referred to simply as "compound C").

[0455] Compound C is preferably a compound that generates an acid, a base or a radical under active light such as ultraviolet light and visible light. As compound C, known photoacid generators, photobase generators and photoradical polymerization initiators (photoradical generators) can be used. Among them, photoacid generators are preferred.

[0456] --Photoacid generator--

[0457] From the viewpoint of resolution, the thermoplastic resin layer may contain a photoacid generator.

[0458] Examples of the photoacid generator include the photocationic polymerization initiator that may be contained in the above-mentioned photosensitive resin layer, and preferred aspects are also the same except for the aspects described below.

[0459] The photoacid generator preferably contains at least one compound selected from an onium salt compound and an oxime sulfonate compound from the viewpoint of sensitivity and resolution, and more preferably contains an oxime sulfonate compound from the viewpoint of sensitivity, resolution and adhesion.

[0460] Furthermore, as the photoacid generator, a photoacid generator having the following structure is also preferred.

[0461] [Chemical formula 3]

[0462]

[0463] --Photoradical polymerization initiator--

[0464] The thermoplastic resin layer may contain a photoradical polymerization initiator.

[0465] Examples of the photoradical polymerization initiator include the photoradical polymerization initiators that may be contained in the above-mentioned photosensitive resin layer, and preferred embodiments are also the same.

[0466] --Photobase Generator--

[0467] The thermoplastic resin layer may contain a photobase generator.

[0468] The photobase generator is not particularly limited as long as it is a known photobase generator, and examples thereof include 2-nitrobenzylcyclohexylcarbamate, triphenylmethanol, O-carbamoylhydroxylamine, O-carbamoyloxime, [[(2,6-dinitrobenzyl)oxy]carbonyl]cyclohexylamine, bis[[(2-nitrobenzyl)oxy]carbonyl]hexane 1,6-diamine, 4-(methylthiobenzoyl)-1-methyl-1-morpholinoethane, (4-morpholinobenzoyl)-1-methyl-1-morpholinoethane, and the like. -1-benzyl-1-dimethylaminopropane, N-(2-nitrobenzyloxycarbonyl)pyrrolidine, hexaminecobalt(III) tris(triphenylmethylborate), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, 2,6-dimethyl-3,5-diacetyl-4-(2-nitrophenyl)-1,4-dihydropyridine and 2,6-dimethyl-3,5-diacetyl-4-(2,4-dinitrophenyl)-1,4-dihydropyridine.

[0469] Compound C may be used alone or in combination of two or more. From the viewpoint of visibility and resolution of the exposed and non-exposed portions, the content of compound C in the thermoplastic resin layer is preferably 0.1% to 10% by mass, more preferably 0.5% to 5% by mass, relative to the total solid content of the thermoplastic resin layer.

[0470] -Plasticizer-

[0471] The thermoplastic resin layer preferably contains a plasticizer from the viewpoints of resolution, adhesion to an adjacent layer, and developability.

[0472] The plasticizer preferably has a molecular weight (in the case of an oligomer or a polymer, a weight average molecular weight (Mw)) smaller than that of the alkali-soluble resin. The molecular weight (weight average molecular weight (Mw)) of the plasticizer is preferably 200 to 2,000.

[0473] As long as the plasticizer is a compound that is compatible with the alkali-soluble resin and expresses plasticity, there is no particular limitation. From the viewpoint of imparting plasticity, the plasticizer preferably has an alkylene oxide in the molecule, and more preferably a polyalkylene glycol compound. The alkylene oxide contained in the plasticizer more preferably has a polyethoxy structure or a polypropylene oxide structure. From the viewpoint of resolution and storage stability, the plasticizer preferably contains a (meth) acrylate compound. From the viewpoint of compatibility, resolution and adhesion to adjacent layers, it is more preferred that the alkali-soluble resin is an acrylic resin and the plasticizer contains a (meth) acrylate compound.

[0474] Examples of the (meth)acrylate compound used as the plasticizer include the (meth)acrylate compounds described as the polymerizable compound contained in the above-mentioned photosensitive resin layer.

[0475] In the photosensitive transfer material, when the thermoplastic resin layer and the photosensitive resin layer are directly contacted and laminated, it is preferred that the thermoplastic resin layer and the photosensitive resin layer contain the same (meth)acrylate compound. This is because the diffusion of components between the layers can be suppressed and the storage stability can be improved by the thermoplastic resin layer and the photosensitive resin layer respectively containing the same (meth)acrylate compound.

[0476] When the thermoplastic resin layer contains a (meth)acrylate compound as a plasticizer, it is preferred that the (meth)acrylate compound is not polymerized even in the exposed portion after exposure from the viewpoint of adhesion with the adjacent layer.

[0477] The (meth)acrylate compound used as the plasticizer is preferably a polyfunctional (meth)acrylate compound having two or more (meth)acryloyl groups in one molecule from the viewpoints of resolution, adhesion to an adjacent layer, and developability.

[0478] Furthermore, as the (meth)acrylate compound used as the plasticizer, a (meth)acrylate compound or a urethane (meth)acrylate compound having an acid group is also preferred.

[0479] The thermoplastic resin layer may contain one plasticizer alone or two or more. From the viewpoint of resolution, adhesion to adjacent layers and developability, the content of the plasticizer is preferably 1% to 70% by mass, more preferably 10% to 60% by mass, and particularly preferably 20% to 50% by mass relative to the gross mass of the thermoplastic resin layer.

[0480] -Surfactant-

[0481] From the viewpoint of thickness uniformity, the thermoplastic resin layer preferably contains a surfactant.

[0482] Examples of the surfactant include the surfactants that may be contained in the above-mentioned photosensitive resin layer, and preferred aspects are also the same.

[0483] The thermoplastic resin layer may contain one surfactant alone or two or more surfactants. The content of the surfactant is preferably 0.001% to 10% by mass, more preferably 0.01% to 3% by mass, based on the total mass of the thermoplastic resin layer.

[0484] -Sensitizer-

[0485] The thermoplastic resin layer may contain a sensitizer.

[0486] The sensitizer is not particularly limited, and examples thereof include the sensitizers that can be contained in the above-mentioned photosensitive resin layer.

[0487] The thermoplastic resin layer may contain one sensitizer alone or two or more. The content of the sensitizer can be appropriately selected according to the purpose, and is preferably in the range of 0.01% to 5% by mass, more preferably in the range of 0.05% to 1% by mass, relative to the total mass of the thermoplastic resin layer, from the viewpoint of improving the sensitivity to the light source and the visibility of the exposed and non-exposed parts.

[0488] -Additives, etc.-

[0489] The thermoplastic resin layer may contain known additives in addition to the above-mentioned components as necessary.

[0490] In addition, the thermoplastic resin layer is described in paragraphs 0189 to 0193 of Japanese Patent Application Laid-Open No. 2014-85643, and the contents described in the publication are incorporated into the present specification.

[0491] ~Physical properties, etc.~

[0492] The thickness of the thermoplastic resin layer is not particularly limited, and is preferably 1 μm or more, and more preferably 2 μm or more. If the thickness is within the above range, the adhesion with the adjacent layer becomes better. In addition, the upper limit of the thickness of the thermoplastic resin layer is not particularly limited, and is preferably 20 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less from the viewpoint of developability and resolution.

[0493] ~Formation method~

[0494] The method for forming the thermoplastic resin layer is not particularly limited as long as it is a method that can form a layer containing the above-mentioned components. As the method for forming the thermoplastic resin layer, for example, there can be mentioned a method of forming by preparing a thermoplastic resin composition containing the above-mentioned components and a solvent, applying the thermoplastic resin composition to the surface of a temporary support, etc., and drying the coating film of the thermoplastic resin composition.

[0495] The thermoplastic resin composition preferably contains a solvent in order to adjust the viscosity of the thermoplastic resin composition and to facilitate formation of a thermoplastic resin layer.

[0496] (Solvent)

[0497] The solvent contained in the thermoplastic resin composition is not particularly limited as long as it can dissolve or disperse the above components contained in the thermoplastic resin layer. The solvent contained in the thermoplastic resin composition includes solvents that can be used for the above-mentioned photosensitive resin composition, and the preferred embodiments are also the same.

[0498] The solvent may be used alone or in combination of two or more.

[0499] The content of the solvent when applying the thermoplastic resin composition is preferably 50% by mass to 1,900% by mass, more preferably 100% by mass to 900% by mass, based on the total solid content in the thermoplastic resin composition.

[0500] The preparation of the thermoplastic resin composition and the formation of the thermoplastic resin layer may be carried out according to the above-mentioned method for preparing the photosensitive resin composition and the method for forming the photosensitive resin layer.

[0501] For example, after preparing a thermoplastic resin composition by dissolving each component contained in the thermoplastic resin layer in the above-mentioned solvent in advance and mixing the obtained solution in a predetermined ratio,

[0502] The obtained thermoplastic resin composition is applied onto the surface of a temporary support, and the coating film of the thermoplastic resin composition is dried to form a thermoplastic resin layer.

[0503] Furthermore, after forming a photosensitive resin layer and an intermediate layer on a cover film described later, a thermoplastic resin layer may be formed on the surface of the intermediate layer.

[0504] (Middle layer)

[0505] The photosensitive transfer material preferably further comprises an intermediate layer between the thermoplastic resin layer and the photosensitive resin layer, for example. By comprising the intermediate layer, mixing of components during coating of multiple layers and during storage after coating can be suppressed.

[0506] The intermediate layer is preferably a water-soluble layer from the viewpoint of developability and suppression of mixing of components when coating multiple layers and during storage after coating.

[0507] The term "water-soluble" means that the solubility in 100 g of water at pH 7.0 at a liquid temperature of 22°C is 0.1 g or more.

[0508] The intermediate layer may be an oxygen barrier layer having an oxygen barrier function described as a "separation layer" in Japanese Patent Application Laid-Open No. 5-72724. If the intermediate layer is an oxygen barrier layer, the sensitivity during exposure is improved, the time load of the exposure machine is reduced, and the productivity is improved, so it is preferred.

[0509] The oxygen barrier layer used as the intermediate layer may be appropriately selected from known layers described in the above-mentioned publications, etc. Among them, an oxygen barrier layer having low oxygen permeability and being dispersed or dissolved in water or an alkaline aqueous solution (a 1 mass % aqueous solution of sodium carbonate at 22° C.) is preferred.

[0510] The intermediate layer preferably contains a resin.

[0511] Examples of the resin contained in the intermediate layer include polyvinyl alcohol resins, polyvinyl pyrrolidone resins, cellulose resins, acrylamide resins, polyethylene oxide resins, gelatin, vinyl ether resins, polyamide resins, and copolymers thereof.

[0512] As the resin contained in the intermediate layer, a water-soluble resin is preferable.

[0513] Furthermore, from the viewpoint of suppressing mixing of components between multiple layers, the resin contained in the intermediate layer is preferably a resin different from either the polymer A contained in the photosensitive resin layer or the thermoplastic resin (alkali-soluble resin) contained in the thermoplastic resin layer.

[0514] From the viewpoint of oxygen barrier properties and suppression of mixing of components during coating of multiple layers and storage after coating, the intermediate layer preferably contains polyvinyl alcohol, and more preferably contains both polyvinyl alcohol and polyvinyl pyrrolidone.

[0515] The intermediate layer may contain the above resins alone or in combination of two or more.

[0516] The content of the resin in the intermediate layer is not particularly limited. From the viewpoint of oxygen barrier properties and suppression of mixing of components when multiple layers are coated and stored after coating, it is preferably 50% to 100% by mass, more preferably 70% to 100% by mass, further preferably 80% to 100% by mass, and particularly preferably 90% to 100% by mass, relative to the total mass of the intermediate layer.

[0517] Furthermore, the intermediate layer may contain additives such as a surfactant as necessary.

[0518] The thickness of the intermediate layer is not particularly limited, but is preferably 0.1 μm to 5 μm, and more preferably 0.5 μm to 3 μm. This is because if the thickness of the intermediate layer is within the above range, the oxygen barrier property will not be reduced, the mixing of components during coating of multiple layers and during storage after coating can be suppressed, and the increase in the time of removing the intermediate layer during development can be suppressed.

[0519] The method for forming the intermediate layer is not particularly limited. For example, an intermediate layer composition containing the above-mentioned resin and any additives is prepared, applied on the surface of the thermoplastic resin layer or the photosensitive resin layer, and the coating film of the intermediate layer composition is dried to form the intermediate layer.

[0520] The intermediate layer composition adjusts the viscosity of the thermoplastic resin composition and preferably contains a solvent in order to facilitate formation of the thermoplastic resin layer.

[0521] The solvent contained in the intermediate layer composition is not particularly limited as long as it can dissolve or disperse the above-mentioned resin, but is preferably at least one selected from water and a water-miscible organic solvent, and more preferably water or a mixed solvent of water and a water-miscible organic solvent.

[0522] Examples of the water-miscible organic solvent include alcohols having 1 to 3 carbon atoms, acetone, ethylene glycol, and glycerol. Alcohols having 1 to 3 carbon atoms are preferred, and methanol or ethanol is more preferred.

[0523] (covering film)

[0524] The photosensitive transfer material preferably has a cover film (protective film) on the side of the photosensitive resin layer opposite to the side facing the temporary support.

[0525] In addition, hereinafter, the surface of the photosensitive resin layer facing the temporary support is referred to as a “first surface”, and the surface of the photosensitive resin layer opposite to the first surface is referred to as a “second surface”.

[0526] As the cover film, resin films and paper can be cited, and resin films are preferred from the viewpoint of strength and flexibility. As the resin film, polyethylene film, polypropylene film, polyethylene terephthalate film, triacetylcellulose film, polystyrene film, and polycarbonate film can be cited. Among them, polyethylene film, polypropylene film, or polyethylene terephthalate film is preferred.

[0527] The thickness of the cover film is not particularly limited, but is preferably 5 μm to 100 μm, and more preferably 10 μm to 50 μm.

[0528] The arithmetic mean roughness Ra value of the surface of the cover film in contact with the photosensitive resin layer (hereinafter, also referred to as the "surface of the cover film") is preferably 0.3 μm or less, more preferably 0.1 μm or less, and further preferably 0.05 μm or less. If the Ra value is 0.3 μm or less, the uniformity of the thickness of the photosensitive resin layer and the formed resin pattern is improved, and the resolution becomes better. The lower limit of the Ra value of the surface of the cover film is not particularly limited, and is preferably 0.001 μm or more.

[0529] The Ra value of the surface of the coating film is measured by the following method.

[0530] The surface of the covering film was measured under the following conditions using a three-dimensional optical analyzer (New View 7300, manufactured by Zygo) to obtain the surface profile of the optical film. As the measurement and analysis software, Microscope Application of MetroPro ver8.3.2 was used. Next, the Surface Map screen was displayed by the analysis software, and histogram data was obtained in the Surface Map screen. The arithmetic mean roughness was calculated from the obtained histogram data to obtain the Ra value of the surface of the covering film. In the case where the covering film is bonded to the photosensitive transfer material, the covering film is peeled off from the photosensitive transfer material, and the Ra value of the peeled surface of the covering film is measured.

[0531] In addition to the above-mentioned layers, the photosensitive transfer material may have, for example, a contrast enhancement layer. The contrast enhancement layer is described in paragraph 0134 of International Publication No. 2018 / 179640. In addition, the photosensitive transfer material may have other layers described in paragraphs 0194 to 0196 of Japanese Patent Publication No. 2014-85643, and the contents described in the publication are incorporated into this specification.

[0532] - Method for producing photosensitive transfer material -

[0533] The photosensitive transfer material can be produced by a known production method.

[0534] Below, while referring to Figure 1 , while explaining the method for producing the photosensitive transfer material. However, the photosensitive transfer material in the present invention is not limited to Figure 1 Materials of the structures shown.

[0535] Figure 1 This is a schematic cross-sectional view showing an example of the structure of a photosensitive transfer material.

[0536] like Figure 1 As shown, the photosensitive transfer material 100 has a structure in which a temporary support 10, a thermoplastic resin layer 12, an intermediate layer 14, a photosensitive resin layer 16 and a cover film 18 are stacked in this order. Figure 1 The structure of the thermoplastic resin layer 12 and the intermediate layer 14 in the embodiment may be, for example, a structure in which the temporary support 10, the photosensitive resin layer 16, and the cover film 18 are stacked in this order.

[0537] The manufacture of the photosensitive transfer material 100 can be carried out, for example, by a method including the following steps: a step of applying a thermoplastic resin composition to the surface of a temporary support 10 and then drying the coating of the thermoplastic resin composition to form a thermoplastic resin layer 12; a step of applying an intermediate layer composition to the surface of the thermoplastic resin layer 12 and then drying the coating of the intermediate layer composition to form an intermediate layer 14; and a step of applying a photosensitive resin composition containing a polymer A and a polymerizable compound B to the surface of the intermediate layer 14 and then drying the coating of the photosensitive resin composition to form a photosensitive resin layer 16.

[0538] In the above-mentioned production method, it is preferred to use a thermoplastic resin composition containing at least one selected from an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent, an intermediate layer composition containing at least one selected from water and a water-miscible organic solvent, and a photosensitive resin composition containing a polymer A, a polymerizable compound B, and at least one selected from an alkylene glycol ether solvent and an alkylene glycol ether acetate solvent. Thus,

[0539] The mixing of components contained in the thermoplastic resin layer 12 and components contained in the intermediate layer 14 during storage of the laminate having a coating film of the intermediate layer composition applied on the surface of the thermoplastic resin layer 12 and / or the intermediate layer composition can be suppressed. Furthermore, the mixing of components contained in the intermediate layer 14 and components contained in the photosensitive resin layer 16 during storage of the laminate having a coating film of the intermediate layer composition applied on the surface of the intermediate layer 14 and / or the intermediate layer composition can be suppressed.

[0540] The photosensitive transfer material 100 is manufactured by pressing the cover film 18 and the photosensitive resin layer 16 of the laminate.

[0541] As a method for manufacturing a photosensitive transfer material, it is preferred to manufacture a photosensitive transfer material 100 including a temporary support 10, a thermoplastic resin layer 12, an intermediate layer 14, a photosensitive resin layer 16 and a cover film 18 by including a step of providing a cover film 18 in contact with the second surface of the photosensitive resin layer 16.

[0542] After manufacturing the photosensitive transfer material 100, a roll-shaped photosensitive transfer material can be produced and stored by winding up the photosensitive transfer material 100. The roll-shaped photosensitive transfer material can be provided as it is in a laminating step with a substrate in a roll-to-roll method described later.

[0543] <Method for producing resin pattern, method for producing circuit wiring>

[0544] The method for manufacturing a resin pattern of the present invention includes: a step of laminating the photosensitive transfer material of the present invention described above to a transferred substrate to thereby arrange a photosensitive resin layer on the transferred substrate (hereinafter also referred to as a “laminating step”); a step of exposing the photosensitive resin layer to pattern exposure (hereinafter also referred to as an “exposure step”); and a step of developing the photosensitive resin layer to form a resin pattern (hereinafter also referred to as a “developing step”).

[0545] The method for producing a resin pattern of the present invention is preferably an embodiment including a step of peeling and removing the resin pattern.

[0546] The method for manufacturing circuit wiring of the present invention includes: a step of laminating the photosensitive transfer material of the present invention described above to a transferred substrate having a conductive layer to configure a photosensitive resin layer on the transferred substrate (hereinafter also referred to as a "laminating step"), a step of exposing the photosensitive resin layer to pattern exposure (hereinafter also referred to as an "exposure step"), a step of developing the photosensitive resin layer to form a resin pattern (hereinafter also referred to as a "developing step"), a step of etching the conductive layer in an area where the resin pattern is not configured to form circuit wiring (hereinafter also referred to as an "etching step"); and a step of peeling off and removing the resin pattern (hereinafter also referred to as a "peeling step").

[0547] The method for producing a circuit wiring of the present invention may include a peeling step after any of the exposure step, the development step, and the etching step.

[0548] The method for producing the resin pattern is not particularly limited as long as it is a method for producing the resin pattern using the above-mentioned photosensitive transfer material.

[0549] As a method for manufacturing a resin pattern, it is preferred that the method sequentially includes a step of laminating a photosensitive transfer material and a transferred substrate (preferably a conductive substrate) by bringing the transferred substrate into contact with the second surface of the photosensitive resin layer, that is, the surface on the side not opposite to the temporary support body (laminating step), a step of exposing the photosensitive resin layer in a pattern (exposure step), and a step of developing the exposed photosensitive resin layer to form a resin pattern (development step).

[0550] The method for producing the circuit wiring is not particularly limited as long as it is a method for producing the circuit wiring using the above-mentioned photosensitive transfer material.

[0551] As a method for manufacturing circuit wiring, it is preferred to include a method comprising a step of etching the conductive layer in an area where a resin pattern is not configured in a stacked body in which a transferred substrate, a conductive layer, and a resin pattern manufactured using the above-mentioned photosensitive transfer material are stacked in sequence (hereinafter also referred to as an "etching step"), and it is more preferred to use a resin pattern manufactured by a manufacturing method including the above-mentioned lamination step, the above-mentioned exposure step, and the above-mentioned development step.

[0552] The following describes the steps of a method for manufacturing a resin pattern and a method for manufacturing circuit wiring. However, unless otherwise specified, the contents described for the steps in the method for manufacturing a resin pattern also apply to the steps in the method for manufacturing circuit wiring.

[0553] 〔Lamination process〕

[0554] The method for manufacturing the resin pattern includes a lamination step.

[0555] In the laminating process, it is preferred to bring the transferred substrate (the conductive layer when a conductive layer is provided on the surface of the transferred substrate) into contact with the second surface of the photosensitive resin layer to press-bond the photosensitive transfer material and the transferred substrate. In the above-mentioned embodiment, in order to improve the adhesion between the second surface of the photosensitive resin layer and the transferred substrate, it can be preferably used as an etching resist when etching the conductive layer of the photosensitive resin layer formed by the pattern after exposure and development.

[0556] In addition, when the photosensitive transfer material has a cover film, the cover film may be removed from the surface of the photosensitive resin layer before lamination.

[0557] Furthermore, the lamination process is as follows: when the surface of the photosensitive resin layer on the side opposite to the temporary support of the photosensitive transfer material also has a layer other than the covering film (for example, a high refractive index layer and / or a low refractive index layer), the surface of the photosensitive resin layer on the side not having the temporary support and the transferred substrate are laminated via the layer.

[0558] There are no particular limitations on the method for pressure-bonding the transferred substrate and the photosensitive transfer material, and a known transfer method and lamination method can be used.

[0559] The photosensitive transfer material and the transferred substrate are preferably laminated by laminating the transferred substrate on the second side of the photosensitive resin layer and applying pressure and heating using a roller or other device. For lamination, a known laminator such as a laminator, a vacuum laminator, and an automatic cutting laminator that can further improve productivity can be used.

[0560] The method for producing a resin pattern and a method for producing a circuit wiring including the laminating step are preferably performed by a roll-to-roll method.

[0561] The roll-to-roll method is described below.

[0562] The roll-to-roll method refers to the following method: a substrate that can be rolled up and unwound is used as the transferred substrate, including a process of unwinding a structure containing a substrate or a substrate before any process included in the method for manufacturing a resin pattern or a method for manufacturing circuit wiring (also referred to as an "unwinding process") and a process of winding up a structure containing a substrate or a substrate after any process (also referred to as a "winding process"), and at least any process (preferably all processes except all processes or a heating process) is performed while carrying a structure containing a substrate or a substrate.

[0563] The unwinding method in the unwinding step and the winding method in the winding step are not particularly limited, and a known method may be used in a production method to which a roll-to-roll system is applied.

[0564] -Transfer substrate-

[0565] As the transfer substrate used for forming the resin pattern using the photosensitive transfer material according to the present invention, a known transfer substrate may be used, and a substrate having a conductive layer is preferred, and a substrate having a conductive layer on its surface is more preferred.

[0566] The transferred substrate may have any layer other than the conductive layer as necessary.

[0567] Examples of the transferred substrate include glass, silicon, and thin films.

[0568] The transfer substrate is preferably transparent. "Transparent" means a property in which the transmittance of light having a wavelength of 400 nm to 700 nm is 80% or more.

[0569] The refractive index of the transferred substrate is preferably 1.50 to 1.52.

[0570] Examples of the transparent glass substrate include tempered glass represented by Gorilla Glass from Corning Incorporated Co., Ltd. Also, materials used in Japanese Patent Application Laid-Open Nos. 2010-86684, 2010-152809, and 2010-257492 can be used as the transparent glass substrate.

[0571] When a film substrate is used as the substrate, it is preferred to use a film substrate with small optical distortion and / or high transparency. Examples of such film substrates include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), triacetyl cellulose (TAC), and cycloolefin polymer (COP).

[0572] As the transfer substrate when producing by a roll-to-roll method, a film is preferred. When producing the circuit wiring for a touch panel by a roll-to-roll method, the transfer substrate is preferably a sheet-like resin composition.

[0573] Examples of the conductive layer that the transfer substrate has include conductive layers used for general circuit wiring and touch panel wiring.

[0574] As the conductive layer, from the viewpoint of conductivity and fine line formability, it is preferably at least one layer selected from a metal layer, a conductive metal oxide layer, a graphene layer, a carbon nanotube layer, a metal nanofiber layer and a conductive polymer layer, more preferably a metal layer, and further preferably a copper layer or a silver layer.

[0575] The transfer substrate may have a single conductive layer or may have two or more conductive layers. When having two or more conductive layers, the conductive layers are preferably made of different materials.

[0576] Examples of the material for the conductive layer include metals and conductive metal oxides.

[0577] Examples of the metal include Al, Zn, Cu, Fe, Ni, Cr, Mo, Ag, and Au.

[0578] As conductive metal oxides, ITO (Indium Tin Oxide), IZO (Indium Zinc Oxide) and SiO 2 .

[0579] In this specification, "conductive" means a volume resistivity of less than 1×10 6 Ωcm. The volume resistivity of the conductive metal oxide is preferably less than 1×10 4 Ωcm.

[0580] When a resin pattern is produced using a transferred substrate having a plurality of conductive layers, it is preferred that at least one of the plurality of conductive layers contains a conductive metal oxide.

[0581] As the conductive layer, an electrode pattern of a sensor corresponding to a visual recognition portion used in a capacitive touch panel or wiring of a peripheral lead portion is preferable.

[0582] [Exposure process]

[0583] The method for producing a resin pattern includes a step of pattern-exposing the photosensitive resin layer after the above-mentioned lamination step (exposure step).

[0584] The detailed configuration and specific size of the pattern in the pattern exposure are not particularly limited. In order to improve the display quality of a display device (e.g., a touch panel) having an input device having circuit wiring manufactured by the circuit wiring manufacturing method and reduce the area occupied by the lead wiring, it is preferred that at least a portion of the pattern (preferably the electrode pattern of the touch panel and / or the lead wiring portion) includes a fine line with a width of 20 μm or less, and more preferably includes a fine line with a width of 10 μm or less.

[0585] The light source used for exposure can be appropriately selected and used as long as it radiates light of a wavelength (for example, 365 nm or 405 nm) capable of exposing the photosensitive resin layer. Specific examples include ultra-high pressure mercury lamps, high pressure mercury lamps, metal halide lamps, and LEDs (Light Emitting Diodes).

[0586] The exposure dose is preferably 5 mJ / cm 2 ~200mJ / cm 2 , more preferably 10 mJ / cm 2 ~100mJ / cm 2 .

[0587] In the exposure process, the pattern exposure can be performed after the temporary support is peeled off from the photosensitive resin layer, or the temporary support can be peeled off after the pattern exposure is performed via the temporary support before the temporary support is peeled off. In the case of peeling off the temporary support before exposure, the mask can be exposed in contact with the photosensitive layer, or it can be exposed close to the exposure without contact. In the case of exposure without peeling off the temporary support, the mask can be exposed in contact with the temporary support, or it can be exposed close to the exposure without contact. In order to prevent mask contamination caused by the contact between the photosensitive resin layer and the mask and to avoid the influence of exposure caused by impurities attached to the mask, it is preferred not to peel off the temporary support and pattern exposure. In addition, when the exposure method is contact exposure, in the case of contact exposure method and non-contact exposure method, it is possible to appropriately select a close exposure method, a projection exposure method of a lens system or a reflector system, a direct exposure method using an exposure laser, etc. and use it. In the case of projection exposure of a reflector of a lens system, an exposure machine with an appropriate lens aperture number (NA) can be used according to the required resolution and depth of focus. In the case of direct exposure, the photosensitive layer can be directly drawn or reduced projection exposure can be performed on the photosensitive layer through a lens. Moreover, exposure can be performed not only in the atmosphere but also under reduced pressure or vacuum, and liquid such as water can be inserted between the light source and the photosensitive layer for exposure.

[0588] 〔Development process〕

[0589] The method for producing a resin pattern includes, after the exposure step, a step of developing the exposed photosensitive resin layer to form a resin pattern (development step).

[0590] When the photosensitive transfer material has a thermoplastic resin and an intermediate layer, the thermoplastic resin layer and the intermediate layer in the non-exposed area are also removed together with the photosensitive resin layer in the non-exposed area in the development step. In addition, in the development step, the thermoplastic resin layer and the intermediate layer in the exposed area can also be removed in the form of being dissolved or dispersed in the developer.

[0591] The development of the exposed photosensitive resin layer in the development step can be performed using a developer.

[0592] The developer is not particularly limited as long as it can remove the non-image area (non-exposed area) of the photosensitive resin layer, and for example, a known developer such as a developer described in Japanese Patent Application Laid-Open No. 5-72724 can be used.

[0593] As a developer, an alkaline aqueous solution containing a compound with pKa=7 to 13 at a concentration of 0.05 to 5 mol / L (liter) is preferred. The developer may contain a water-soluble organic solvent and / or a surfactant. As a developer, the developer described in paragraph 0194 of International Publication No. 2015 / 093271 is also preferred.

[0594] The developing method is not particularly limited, and may be any of puddle developing, shower developing, shower and spin developing, and immersion developing. Shower developing is a developing process in which a developer is sprayed onto the exposed photosensitive resin layer to remove the unexposed portion.

[0595] After the development step, it is preferred to remove the development residue by spraying a cleaning agent and wiping with a brush.

[0596] The liquid temperature of the developer is not particularly limited, but is preferably 20 to 40°C.

[0597] 〔Etching process〕

[0598] The method for manufacturing circuit wiring includes a step (etching step) of etching the conductive layer in an area where a resin pattern is not configured in a stacked body in which a transferred substrate, a conductive layer and a resin pattern (more preferably a resin pattern manufactured by a manufacturing method including the above-mentioned bonding step, the above-mentioned exposure step and the above-mentioned development step) are stacked in sequence.

[0599] In the etching step, the conductive layer is etched using the resin pattern formed by the photosensitive resin layer as an etching resist.

[0600] As the etching treatment method, a known method can be applied, for example, the method described in paragraphs 0209 to 0210 of Japanese Patent Application Publication No. 2017-120435, the method described in paragraphs 0048 to 0054 of Japanese Patent Application Publication No. 2010-152155, wet etching by immersion in an etching solution, and dry etching methods such as plasma etching can be cited.

[0601] The etching solution used in the wet etching may be an acidic or alkaline etching solution appropriately selected according to the etching target.

[0602] Examples of the acidic etching solution include aqueous solutions of an acidic component selected from hydrochloric acid, sulfuric acid, nitric acid, acetic acid, hydrofluoric acid, oxalic acid, and phosphoric acid alone, and mixed aqueous solutions of an acidic component and a salt selected from ferric chloride, ammonium fluoride, and potassium permanganate. The acidic component may also be a combination of a plurality of acidic components.

[0603] Examples of the alkaline etching solution include aqueous solutions of an alkali component selected from sodium hydroxide, potassium hydroxide, ammonia, organic amines, and salts of organic amines (tetramethylammonium hydroxide, etc.), and mixed aqueous solutions of an alkali component and a salt (potassium permanganate, etc.). The alkali component may also be a combination of multiple alkali components.

[0604] [Peeling process]

[0605] The method for producing a circuit wiring of the present invention includes a step (peeling step) of peeling and removing the remaining cured portion (resin pattern) on the transferred substrate. Furthermore, the method for producing a resin pattern of the present invention may include the peeling step.

[0606] The peeling step can be provided after the exposure step, the development step, and the etching step described above.

[0607] In the present invention, the resin pattern formed by the exposure process, the development process and the etching process is peeled off using the photosensitive transfer material of the present invention, so that the peeled off peeling sheet is difficult to adhere to the device. As a result, the peeling sheet is difficult to accumulate in the device, and the clogging of the piping and the like and the decline of the filtering function can be avoided. In addition, it is also possible to suppress the re-adhesion to the manufactured wiring board.

[0608] As a method for removing the resin pattern of the cured portion remaining as a pattern, there is a method of removing the resin pattern by peeling it off with a chemical treatment. In the case of peeling removal, a method of removing using a peeling liquid is preferred.

[0609] The method of removing the cured layer using a stripping liquid includes immersing the transfer substrate having a resin pattern in a stripping liquid preferably at a temperature of 30 to 80° C. (more preferably 40 to 70° C.) and stirring for 1 to 30 minutes.

[0610] As the stripping liquid, an alkaline solution (also referred to as an alkaline stripping liquid) can be used.

[0611] Examples of the alkaline solution include a stripping solution prepared by dissolving an inorganic alkaline component or an organic alkaline component in water, dimethyl sulfoxide, N-methylpyrrolidone, or a mixed solution thereof.

[0612] Examples of the inorganic alkali component include sodium hydroxide and potassium hydroxide.

[0613] Examples of the organic base component include primary amine compounds, secondary amine compounds, tertiary amine compounds, and quaternary ammonium salt compounds.

[0614] The resin pattern may be removed by a known method such as a spray method, a shower method, or a spin immersion method using a stripping liquid, other than the above-mentioned immersion method.

[0615] (Other processes)

[0616] The method for producing a circuit wiring may include any steps (other steps) other than the above-mentioned steps. For example, the following steps may be mentioned, but the method is not limited to these steps.

[0617] In addition, as exposure steps, development steps, and other steps that can be applied to the method for manufacturing circuit wiring, there are steps described in paragraphs 0035 to 0051 of Japanese Patent Application Laid-Open No. 2006-23696.

[0618] <Cover film peeling step>

[0619] When the photosensitive transfer material includes a cover film, the method for producing a resin pattern preferably includes a step of peeling the cover film from the photosensitive transfer material. The method for peeling the cover film is not limited, and a known method can be applied.

[0620] <Process for reducing visible light reflectivity>

[0621] The method for producing a circuit wiring may include a step of performing a treatment to reduce the visible light reflectivity of a part or all of the plurality of conductive layers included in the transferred substrate.

[0622] As a treatment for reducing the visible light reflectance, an oxidation treatment can be mentioned. When the transfer substrate has a conductive layer containing copper, the visible light reflectance of the conductive layer can be reduced by oxidation treatment of copper to obtain copper oxide and blackening the conductive layer.

[0623] The process of reducing the visible light reflectance is described in paragraphs 0017 to 0025 of Japanese Patent Application Laid-Open No. 2014-150118 and paragraphs 0041, 0042, 0048, and 0058 of Japanese Patent Application Laid-Open No. 2013-206315, and the contents described in these publications are incorporated into this specification.

[0624] <Step of forming an insulating film, step of forming a new conductive layer on the surface of the insulating film>

[0625] The method for manufacturing a circuit wiring preferably includes a step of forming an insulating film on the surface of the circuit wiring and a step of forming a new conductive layer on the surface of the insulating film. Through the above steps, a second electrode pattern insulated from the first electrode pattern can be formed.

[0626] The step of forming the insulating film is not particularly limited, and a known method of forming a permanent film may be used. Alternatively, an insulating film having a desired pattern may be formed by photolithography using a photosensitive material having insulating properties.

[0627] The step of forming a new conductive layer on the insulating film is not particularly limited. For example, a new conductive layer having a desired pattern can be formed by photolithography using a photosensitive material having conductivity.

[0628] The manufacturing method of the circuit wiring also preferably uses a transferred substrate having a plurality of conductive layers on both surfaces of the substrate to form a circuit on the conductive layers formed on both surfaces of the transferred substrate one by one or simultaneously. With this structure, a touch panel circuit wiring can be formed in which a first conductive pattern is formed on one surface of the transferred substrate and a second conductive pattern is formed on the other surface. In addition, it is also preferred that the touch panel circuit wiring of this structure is formed from both sides of the transferred substrate in a roll-to-roll manner.

[0629] ~Application of circuit wiring~

[0630] The circuit wiring manufactured by the manufacturing method of the circuit wiring can be applied to various devices. As a device having the circuit wiring manufactured by the above-mentioned manufacturing method, for example, an input device can be cited, preferably a touch panel, and more preferably an electrostatic capacitance touch panel. In addition, the above-mentioned input device can be applied to display devices such as organic EL display devices and liquid crystal display devices.

[0631] [Method for manufacturing touch panel]

[0632] The method for producing a touch panel is not particularly limited as long as it is a method for producing a touch panel using the above-mentioned photosensitive transfer material.

[0633] As a method for manufacturing a touch panel, it is preferred that the method include a step of forming wiring for the touch panel by etching the conductive layer in an area where the resin pattern is not configured in a stacked body in which a transferred substrate, a conductive layer and a resin pattern manufactured using the above-mentioned photosensitive transfer material are stacked in sequence, and it is more preferred to use a resin pattern manufactured by a manufacturing method including the above-mentioned lamination step, the above-mentioned exposure step and the above-mentioned development step.

[0634] The specific aspects of each step in the method for manufacturing a touch panel and the order of performing each step are as described in the above section of “the method for manufacturing a circuit wiring”, and the preferred aspects are also the same.

[0635] In the method for manufacturing a touch panel, the touch panel wiring is formed by the above-mentioned method, and other aspects may be referred to a known method for manufacturing a touch panel.

[0636] Furthermore, the method for manufacturing a touch panel may include any steps (other steps) other than the above steps.

[0637] Figure 2 and Figure 3 An example of a mask pattern used in manufacturing a touch panel is shown.

[0638] Figure 2 The pattern A and Figure 3 In the pattern B shown in FIG. 1 , SL and G are non-image portions (light shielding portions), and DL is a frame body for virtual alignment. Figure 2 By exposing the photosensitive resin layer through a mask of pattern A shown in FIG. 1 , a touch panel having circuit wiring of pattern A corresponding to SL and G can be manufactured. Specifically, the touch panel can be formed by the method of International Publication No. 2016 / 190405. Figure 1 In one example of the touch panel produced, G is a portion where a transparent electrode (touch panel electrode) is formed, and SL is a portion where wiring of a peripheral lead-out portion is formed.

[0639] By the above touch panel manufacturing method, a touch panel having at least touch panel wiring is manufactured. The touch panel preferably has a transparent substrate, an electrode, and an insulating layer or a protective layer.

[0640] As a detection method in a touch panel, a resistance film method, an electrostatic capacitance method, an ultrasonic method, an electromagnetic induction method, an optical method, etc. are mentioned, Among them, the electrostatic capacitance method is preferable.

[0641] Examples of the touch panel type include a so-called in-cell type (for example, the touch panel described in FIGS. 5, 6, 7, and 8 of Japanese Unexamined Patent Application Publication No. 2012-517051), a so-called out-cell type (for example, the touch panel described in FIG. 19 of Japanese Unexamined Patent Application Publication No. 2013-168125 and the touch panel described in FIG. 2012-89102). Figure 1 5), OGS (One Glass Solution) type, TOL (Touch-on-Lens) type (for example, Japanese Patent Application Laid-Open No. 2013-54727) Figure 2 ), various plug-in types (so-called GG, G1·G2, GFF, GF2, GF1, G1F, etc.), and other structures (for example, the structure described in FIG. 6 of Japanese Patent Application Publication No. 2013-164871).

[0642] As an example of a touch panel, there can be mentioned the touch panel described in paragraph 0229 of Japanese Patent Application Laid-Open No. 2017-120345.

[0643] Example

[0644] Hereinafter, the present invention will be described in further detail with reference to examples, but the present invention is not limited to the following examples.

[0645] The details of the materials used in Examples and Comparative Examples are shown below.

[0646] (A) Resin

[0647] A-1: Styrene / methacrylic acid / methyl methacrylate copolymer (=32 / 28 / 40 (mass %), Mw=40,000, acid value=182.5 mgKOH / g, Tg=104°C)

[0648] A-2: Styrene / methacrylic acid / methyl methacrylate copolymer (=52 / 29 / 23 (mass %), Mw=60,000, acid value=189.0 mgKOH / g, Tg=114°C)

[0649] A-3: benzyl methacrylate / methacrylic acid copolymer (=81 / 19 (mass %), Mw=40,000, acid value=123.8 mgKOH / g, Tg=77°C)

[0650] A-4: propylene glycol monomethyl ether acetate solution of benzyl methacrylate, methacrylic acid and acrylic acid copolymer (solid content concentration 30.0 mass%, Mw = 30000, acid value = 153 mgKOH / g)

[0651] A-5: KURARAY CO., LTD. POVALPVA-205 (KURARAY CO., LTD.)

[0652] A-6: Polyvinylpyrrolidone K-30 (NIPPON SHOKUBAI CO., Ltd.)

[0653] (B) Polymerizable Compounds

[0654] B-1: NK ESTER BPE-500 (ethoxylated bisphenol A dimethacrylate (molecular weight 804), Shin-Nakamura Chemical Co., Ltd.)

[0655] B-2: NK ESTER BPE-200 (ethoxylated bisphenol A dimethacrylate (molecular weight 540), Shin-Nakamura Chemical Co., Ltd.)

[0656] B-3: a dimethacrylate of polyethylene glycol having an average of 15 mol of ethylene oxide and an average of 2 mol of propylene oxide added to both ends of bisphenol A (a compound represented by the above formula (1) (R 1 =R 2 =CH 3 、n 2 =n 4 =2, n 1 =n 3 =15)〕

[0657] B-4: ARONIXM-270 (polypropylene glycol (n≈12) diacrylate, TOAGOSEI Co., Ltd.)

[0658] B-5: NK ESTER A-TMPT (trimethylolpropane triacrylate (molecular weight 296), Shin-Nakamura Chemical Co., Ltd.)

[0659] B-6: Sartomer SR-454 (ethoxylated (3) trimethylolpropane triacrylate, Arkema)

[0660] B-7: Sartomer SR-502 (ethoxylated (9) trimethylolpropane triacrylate, Arkema)

[0661] B-8: NK ESTER A-9300-1CL (ε-caprolactone-modified tris-(2-acryloyloxyethyl) isocyanurate (molecular weight 423), Shin-Nakamura Chemical Co., Ltd.)

[0662] B-9: NK ESTER A-DCP (tricyclodecane dimethanol diacrylate (molecular weight 304), Shin-Nakamura Chemical Co., Ltd.)

[0663] B-10: 8UX-015A (UV-curable urethane acrylate oligomer, Taisei Fine Chemical Co., Ltd.)

[0664] B-11: ARONIXTO-2349 (TOAGOSEI CO., Ltd.)

[0665] (C) Photopolymerization initiator

[0666] C-1: B-CIM (2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, KUROGANEKASEI Co., Ltd.)

[0667] C-2: SB-PI 701 (4,4'-bis(diethylamino)benzophenone, SANYO TRADING CO., LTD.)

[0668] (D) Pigments and additives

[0669] D-1: Colorless crystal violet (Tokyo Chemical Industry Co., Ltd.)

[0670] D-2: N-phenylglycine (Tokyo Chemical Industry Co., Ltd.)

[0671] D-3: Brilliant Green (Tokyo Chemical Industry Co., Ltd.)

[0672] D-4: CBT-1 (Carboxybenzotriazole, JOHOKU CHEMICAL CO., LTD)

[0673] D-5: 1:1 (mass ratio) mixture of 1-(2-di-n-butylaminomethyl)-5-carboxybenzotriazole and 1-(2-di-n-butylaminomethyl)-6-carboxybenzotriazole

[0674] D-6: TDP-G (phenothiazine, Kawaguchi Chemical Industry Co., LTD.; polymerization inhibitor)

[0675] D-7: Irganox 245 (BASF; antioxidant)

[0676] D-8: N-nitrosophenylhydroxylamine aluminum salt (FUJIFILM Wako Pure Chemical Corporation; polymerization inhibitor)

[0677] D-9: Phenidone (Tokyo Chemical Industry Co., Ltd.)

[0678] (E) Surfactant

[0679] E-1:Megaface F-552(DIC CORPORATION)

[0680] E-2:Megaface F-444(DIC CORPORATION)

[0681] (F) Solvent

[0682] F-1: Methyl ethyl ketone (SANKYO CHEMICAL CO., LTD.)

[0683] F-2: Propylene glycol monomethyl ether acetate (SHOWA DENKO KK)

[0684] F-3: Ion exchange water

[0685] F-4: Methanol (MITSUBISHI GAS CHEMICAL COMPANY, INC.)

[0686] (Example 1-1)

[0687] First, an example corresponding to the invention according to the first aspect described above will be described.

[0688] <Preparation of Thermoplastic Resin Composition>

[0689] The thermoplastic resin composition was prepared by mixing the following ingredients.

[0690] A-4: 42.85 parts by mass

[0691] B-9: 4.63 parts by mass

[0692] B-10: 2.31 parts by mass

[0693] B-11: 0.77 parts by mass

[0694] ·E-1: 0.03 parts by mass

[0695] F-1: 39.50 parts by mass

[0696] F-2: 9.51 parts by mass

[0697] Compound of the following structure (photoacid generator, compound synthesized according to the method described in paragraph 0227 of JP-A-2013-47765): 0.32 parts by mass

[0698] [Chemical formula 4]

[0699]

[0700] · Compound of the structure shown below (acid-induced coloring): 0.08 parts by mass

[0701] [Chemical formula 5]

[0702]

[0703] <Preparation of Intermediate Layer Composition>

[0704] The interlayer composition was prepared by mixing the following ingredients.

[0705] A-5: 3.22 parts by mass

[0706] A-6: 1.49 parts by mass

[0707] ·E-2: 0.0015 parts by mass

[0708] F-3: 38.12 parts by mass

[0709] F-4: 57.17 parts by mass

[0710] <Preparation of Photosensitive Resin Composition 1-1>

[0711] The components described in the following Table 1 and Table 2 were mixed to prepare a photosensitive resin composition 1-1.

[0712] <Preparation of Photosensitive Transfer Material 1-1>

[0713] A polyethylene terephthalate (PET) film with a thickness of 30 μm was prepared as a temporary support. The above-mentioned thermoplastic resin composition was applied to the surface of the temporary support using a slit nozzle so that the coating width was set to 1.0 m and the thickness after drying was 4.0 μm. The coating film of the thermoplastic resin composition was dried at 80°C for 40 seconds to form a thermoplastic resin layer. Next, the above-mentioned intermediate layer composition was applied to the surface of the thermoplastic resin layer using a slit nozzle so that the coating width was set to 1.0 m and the thickness after drying was 1.2 μm. The coating film of the intermediate layer composition was dried at 80°C for 40 seconds to form an intermediate layer. Next, the photosensitive resin composition 1-1 was applied to the surface of the intermediate layer using a slit nozzle so that the coating width was set to 1.0 m and the thickness after drying was 3.0 μm. The coating film of the photosensitive resin composition 1-1 was dried at 80°C for 40 seconds to form a photosensitive resin layer. Furthermore, a PET film (Lumirror 16KS40, TORAY INDUSTRIES, INC.) was pressure-bonded as a cover film on the surface of the photosensitive resin layer to prepare a photosensitive transfer material 1-1.

[0714] (Evaluation 1)

[0715] The following measurements and evaluations were performed using the photosensitive transfer material 1-1 prepared in Example 1-1. The results of the measurements and evaluations are shown in Tables 1 and 2.

[0716] -1. Swelling properties-

[0717] (1) Lamination

[0718] As a transfer substrate, a substrate with a copper layer was prepared in which a copper layer with a thickness of 200 nm was formed on a PET film with a thickness of 100 μm by a sputtering method.

[0719] The copper-layered substrate and the photosensitive transfer material 1-1 are arranged so that the surface of the copper layer of the copper-layered substrate and the surface of the photosensitive resin layer of the photosensitive transfer material 1-1 are in contact with each other, and the copper-layered substrate and the photosensitive transfer material 1-1 are bonded together by a sheet laminator.

[0720] The conditions for lamination are as follows.

[0721] <Conditions>

[0722] Roller temperature: 100°C

[0723] Lamination speed: 2m / min

[0724] Lamination pressure: 0.5MPa

[0725] (2) Determination of Eb

[0726] A 15-step wedge (manufactured by FUJIFILM Co., Ltd.) was placed on a temporary support of the photosensitive transfer material 1-1 bonded to the substrate with a copper layer, and an illumination of 20 mW / cm 2 The high pressure mercury lamp was used with an exposure of 180 mJ / cm through a 15-step wedge. 2 The photosensitive resin layer was irradiated with ultraviolet light (UV). After irradiation, the temporary support was peeled off and developed with a 0.9 mass % aqueous solution of sodium carbonate at 25°C for 30 seconds. After that, the thickness of the cured layer (residual film thickness) in the area corresponding to each step was measured, and the number of steps in which the residual film thickness was within the range of ±1% of the thickness of the photosensitive resin layer before development was determined. The exposure amount corresponding to the determined number of steps was set to Eb. As a result, Eb in Example 1-1 was 46 mJ / cm 2 .

[0727] (3) Swelling

[0728] The photosensitive transfer material 1-1 bonded to a glass substrate (manufactured by Eagle-XG Corning Incorporated Co., Ltd.) was exposed to light at an exposure dose Ep of 92 mJ / cm 2 (=2×46mJ / cm 2 ) Through illumination 20mW / cm 2 The entire surface was irradiated with UV light using a high-pressure mercury lamp. The temporary support was peeled off from the irradiated photosensitive transfer material 1-1, and 10 μL of a 10% by mass aqueous solution of monoethanolamine at 50°C was dripped onto the surface of the exposed cured layer. The droplets were removed at 10 seconds from the start of dripping of the 10% by mass aqueous solution of monoethanolamine and at 20 seconds from the start of dripping of the 10% by mass aqueous solution of monoethanolamine, and the thickness (t 10s ) and the thickness of the solidified layer at the dropwise addition point after 20 seconds (t 20s) In addition, the thickness of the solidified layer before dropping of each dropping portion (t b ).

[0729] The swelling ratio was determined from the following formula based on the obtained measured values.

[0730] Swelling ratio after 10 seconds (%) = (t 10s / t b )×100

[0731] Swelling ratio after 20 seconds (%) = (t 20s / t b )×100

[0732] -2. Peel Sheet Adhesion-

[0733] The photosensitive transfer material 1-1 bonded to the substrate with the copper layer was exposed to light at an exposure dose Ep of 92 mJ / cm 2 (=2×46mJ / cm 2 ) Through illumination 20mW / cm 2 The entire surface was irradiated with UV light by a high-pressure mercury lamp. The temporary support was peeled off from the irradiated photosensitive transfer material 1-1, and the laminated product after peeling (laminated product of cured layer / intermediate layer / thermoplastic resin layer) was immersed in a 10% by mass aqueous solution of monoethanolamine at 50°C and stirred together with the substrate with the copper layer, and the laminated product was peeled off from the substrate with the copper layer. In addition, a stripping liquid containing the peeled peeling pieces was injected into a SUS sieve (MANABE KOGYO CO., LTD.) with 150 mesh / 18B steel wire, and the peeling pieces were filtered and removed. By repeating this operation, the peeling pieces were piled up until the amount of the peeling pieces became 1.0 g per 1 square centimeter of SUS mesh. Afterwards, the weight of the peeling pieces that naturally fell from the SUS sieve was measured by turning the SUS sieve 180°, and the stacking surface side of the filtrate of the SUS sieve was facing the vertical downward direction. Using the measured value, the adhesion rate of the peeling pieces was calculated from the following formula. The adhesion rate is the ratio of the amount of the release sheet remaining on the SUS mesh without falling off to the amount of the accumulated release sheet before the front-back reversal.

[0734] The adhesion rate of the peeling sheet (%) = (1-W f / W t )×100

[0735] W f : The quality of the peeling piece that falls

[0736] W t : The total mass of the peeling pieces removed by filtration

[0737] The adhesion of the peeling sheet was evaluated according to the following evaluation criteria based on the adhesion rate value. The evaluation was performed using four grades: A (excellent) > B > C > D (poor). In terms of process suitability, as an adhesion rate evaluation, it is preferably B or above. In addition, the smaller the adhesion rate value, the less likely it is that the peeling sheet will accumulate in the device for peeling the cured layer, and it can be evaluated that the process suitability as a photosensitive transfer material is high.

[0738] <Evaluation Criteria>

[0739] A: Adhesion rate <30%

[0740] B: 30%≤Adhesion rate<50%

[0741] C: 50%≤Adhesion rate<80%

[0742] D: 80% ≤ Adhesion rate

[0743] -3. Stripping time-

[0744] The photosensitive transfer material 1-1 bonded to the substrate with the copper layer was exposed to light at an exposure dose Ep of 92 mJ / cm 2 (=2×46mJ / cm 2 ) Through illumination 20mW / cm 2 The entire surface was irradiated with UV light using a high-pressure mercury lamp. The irradiated photosensitive transfer material 1-1 was cut into 10 cm squares, and the temporary support was peeled off to obtain a test sample. The test sample was immersed in 1 liter of a stirred 10% by mass aqueous solution of monoethanolamine at 50°C, and the time from the time of immersion (start of immersion) to the time when the laminate was completely peeled off from the substrate with the copper layer (end of peeling) was measured. In addition, 1 liter of a 10% by mass aqueous solution of monoethanolamine at 50°C was used instead of 1 liter of a 10% by mass aqueous solution of monoethanolamine at 25°C, and the same measurement was performed.

[0745] (Examples 1-2 to 1-11, Comparative Examples 1 to 3)

[0746] In Example 1-1, except that the photosensitive resin composition 1-1 was replaced with any one selected from the photosensitive resin compositions 1-2 to 1-11 and the photosensitive resin compositions A to C described in Tables 1 and 2 below, and the thickness of the photosensitive resin layer was changed, the photosensitive transfer materials 1-2 to 1-11 and the photosensitive transfer materials A to C were prepared in the same manner as in Example 1-1, and the same measurements and evaluations were performed. The results of the measurements and evaluations are shown in Tables 1 and 2 below.

[0747] [Table 1]

[0748]

[0749] * 1: Alkali soluble resin * 2: Photopolymerization initiator

[0750] [Table 2]

[0751]

[0752] * 1: Alkali soluble resin * 2: Photopolymerization initiator

[0753] As a result of the above evaluation, in Example 1-1, the adhesion rate was 48% (Evaluation B). In addition, in Example 1-1, the peeling time (t 50) is 10 seconds, and the peeling time (t 25 ) is 30 seconds. Therefore, t 25 / t 50 =3.

[0754] As shown in Tables 1 and 2, the photosensitive transfer materials prepared in the examples all had small swelling amounts during peeling and reduced peel sheet adhesion. Therefore, it is believed that the photosensitive transfer materials of the examples have good process suitability when peeling off the resin pattern formed by exposure and development.

[0755] In contrast, in Comparative Examples 1 to 3, the amount of swelling during peeling was greater than that of each Example, and the peeling piece was easily attached.

[0756] (Example 2-1)

[0757] Next, an example corresponding to the invention according to the second aspect described above will be described.

[0758] Photosensitive resin composition 2-1 was prepared by mixing the components described in the following Table 3. Photosensitive transfer material 2-1 was prepared in the same manner as in Example 1-1 except that photosensitive resin composition 2-1 was used instead of photosensitive resin composition 1-1.

[0759] (Rating 2)

[0760] The photosensitive transfer material 2-1 prepared in Example 2-1 was used to perform measurement and evaluation in the same manner as in Example 1-1. Table 3 shows the results of the measurement and evaluation.

[0761] The Eb in Example 2-1 is 58 mJ / cm 2 .

[0762] -4. Peeling method-

[0763] The photosensitive transfer material 2-1 bonded to the substrate with the copper layer was exposed to light at an exposure dose Ep of 116 mJ / cm 2 (=2×58mJ / cm 2 ) Through illumination 20mW / cm 2 The entire surface was irradiated with UV light using a high-pressure mercury lamp. The irradiated photosensitive transfer material 2-1 was cut into 5 cm squares, and the temporary support was peeled off to obtain a test sample. The test sample was kept horizontal and immersed in a 10% by mass aqueous solution of monoethanolamine at 25°C without stirring. In this state, the test sample was left to stand, and the peeling method of the test sample and the time from the time of immersion (start of immersion) to the complete peeling of the laminate from the substrate with the copper layer (end of peeling) were evaluated.

[0764] (Examples 2-2 to 2-6)

[0765] In Example 2-1, except that the photosensitive resin composition 2-1 was replaced with any one of the photosensitive resin compositions 2-2 to 2-6 described in Table 3 below, and the thickness of the photosensitive resin layer was changed, photosensitive transfer materials 2-2 to 2-6 were prepared in the same manner as in Example 2-1, and the same measurements and evaluations were performed. The results of the measurements and evaluations are shown in Table 3 below.

[0766] In addition, the details of Comparative Examples 1 to 3 are as described above.

[0767] [Table 3]

[0768]

[0769] * 1: Alkali soluble resin * 2: Photopolymerization initiator

[0770] As a result of the above evaluation, in the photosensitive transfer material 2-1, the laminate was peeled off from the base material with the copper layer. No curling of the peeled peeling piece was confirmed. In addition, the time until the laminate was peeled off from the base material with the copper layer was 320 seconds. In addition, as shown in Table 3, in the photosensitive transfer materials prepared in Examples 2-2 to 2-6, the peeled peeling pieces were all curled, and it was found that the peeling pieces in the form of small pieces peeled off autonomously.

[0771] Therefore, it is considered that the photosensitive transfer material of the example exhibits good process suitability when the resin pattern formed by exposure and development is peeled off.

[0772] In contrast, in Comparative Examples 1 to 3, autonomous separation was not confirmed in any of the examples.

[0773] (Example 3-1)

[0774] Next, an example corresponding to the invention according to the third aspect described above will be described.

[0775] Photosensitive resin composition 3-1 was prepared by mixing the components described in the following Table 4. Photosensitive transfer material 3-1 was prepared in the same manner as in Example 1-1 except that photosensitive resin composition 3-1 was used instead of photosensitive resin composition 1-1.

[0776] (Rating 3)

[0777] The photosensitive transfer material 3-1 prepared in Example 3-1 was used to perform measurement and evaluation in the same manner as in Example 1-1. Table 4 shows the results of the measurement and evaluation.

[0778] The Eb in Example 3-1 is 46 mJ / om 2 .

[0779] -5. Fatigue fluid-

[0780] The photosensitive transfer material 3-1 bonded to the substrate with the copper layer was exposed to light at an exposure dose Ep of 92 mJ / cm 2 (=2×46mJ / cm 2 ) Through illumination 20mW / cm 2 The entire surface was irradiated with UV light from a high pressure mercury lamp. The irradiated photosensitive transfer material 3-1 was cut into 10 cm squares, and the temporary support was peeled off to obtain a test sample.

[0781] Separately, CO was blown into 1000 mL of a 10% by mass aqueous solution of monoethanolamine at a flow rate of 46 mL / min. 2 The gas was heated for 160 seconds to produce a fatigue fluid simulating degradation.

[0782] Unused monoethanolamine 10 mass % aqueous solution (new solution) and the prepared fatigue solution were used, and the new solution and the fatigue solution were kept at 50°C. Then, the test sample was immersed in the stirred 50°C new solution, and the time (t) from the time of immersion (immersion start) to the time when the laminate was completely peeled off from the substrate with the copper layer (peeling end) was calculated. fr ; In Table 4, it is expressed as "new solution peeling time"). In addition, the test sample was immersed in the stirred fatigue solution, and the time (t) from the time of immersion (immersion start) to the time when the laminate was completely peeled off from the substrate with the copper layer (peeling end) was calculated. fa ; In Table 4, it is expressed as "fatigue liquid stripping time").

[0783] Use the found t fa and t fr , and evaluated whether the following formula was satisfied. The case where the following formula was satisfied was set to "G", and the case where the following formula was not satisfied was set to "N".

[0784] t fa ≤t fr ×1.5

[0785] (Examples 3-2 to 3-6)

[0786] In Example 3-1, except that the photosensitive resin composition 3-1 was replaced with any one of the photosensitive resin compositions 3-2 to 3-6 described in Table 4 below, and the thickness of the photosensitive resin layer was changed, photosensitive transfer materials 3-2 to 3-6 were prepared in the same manner as in Example 3-1, and the same measurements and evaluations were performed. The results of the measurements and evaluations are shown in Table 4 below.

[0787] In addition, the details of Comparative Examples 1 to 3 are as described above.

[0788] [Table 4]

[0789]

[0790] * 1: Alkali soluble resin * 2: Photopolymerization initiator

[0791] As a result of the above evaluation, the peeling time (t fa ) is 15 seconds. Also, when using fatigue fluid, t fa Compared with 1.5t when using unused fluid fr reduce.

[0792] As shown in Table 4, the photosensitive transfer material prepared in the example has a high thermal conductivity even when the stripping liquid is CO 2 Even in the state where the alkalinity is reduced due to fatigue, the peeling property does not change significantly, and the peeling sheet adhesion decreases. Therefore, it is considered that the photosensitive transfer material of the example shows good process suitability when peeling off the resin pattern formed by exposure and development.

[0793] In contrast, in Comparative Examples 1 to 3, the stripping liquid is CO 2 The peeling property is poor when fatigued, and the swelling amount when peeling becomes large. Therefore, the peeling piece is easily attached.

[0794] Furthermore, the following can be understood from Tables 1 to 4 above.

[0795] According to Example 1-3 and Example 2-1, Example 1-6 and Example 2-3, and Example 1-7 and Example 2-4, in the photosensitive transfer material of the examples, the swelling amount during peeling was suppressed to a small extent, and autonomous peeling from the substrate with the copper layer was observed, and the adhesion of the peeling sheet was reduced.

[0796] According to Example 2-2 and Example 3-3, Example 2-3 and Example 3-4, and Example 2-4 and Example 3-5, in the photosensitive transfer material of the examples, it was observed that the material peeled off autonomously from the substrate with the copper layer, and even with a fatigue stripping liquid with reduced alkalinity, the stripping property did not change significantly, and the adhesion of the stripping sheet was reduced.

[0797] According to Example 1-1 and Example 3-1, the photosensitive transfer material of the example has a small swelling amount during peeling, and the peelability does not change significantly even with a fatigue peeling liquid with reduced alkalinity, and the peeling sheet adhesion is reduced.

[0798] According to Examples 1-6, 2-3 and 3-4, and 1-7, 2-4 and 3-5, in the photosensitive transfer material of the examples, the amount of swelling during peeling is suppressed to a small extent, and autonomous peeling from the substrate with the copper layer is observed, and even with a fatigue peeling liquid with reduced alkalinity, the peeling property does not change significantly, and the adhesion of the peeling sheet is well reduced.

[0799] Industrial Applicability

[0800] The photosensitive transfer material of the present invention can be appropriately used for various purposes required for precision microfabrication based on photolithography. After the photosensitive resin layer is patterned, the photosensitive resin layer can be etched as a coating, or electroplating can be performed mainly. In addition, the cured film obtained by patterning the photosensitive resin layer can be used as a permanent film, for example, it can be used as a wiring protection film with an interlayer insulating film, a wiring protection film, an index matching layer, etc. In addition, the photosensitive transfer material of the present invention can be appropriately used for various wiring formation purposes of semiconductor packages, printed substrates, and sensor substrates; touch panels, electromagnetic shielding materials, conductive films such as thin film heaters, liquid crystal sealing materials, formation of structures in the microcomputer field or microelectronics field, etc.

[0801] The disclosure of Japanese Patent Application No. 2020-061104 filed on March 30, 2020 is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described in this specification are incorporated herein by reference as if each document, patent application, and technical standard was specifically and individually described as being incorporated by reference.

Claims

1. A photosensitive transfer material having a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator on a temporary support, The polymerizable compound contains a bifunctional ethylenically unsaturated compound having two ethylenically unsaturated groups in one molecule and a trifunctional ethylenically unsaturated compound having three ethylenically unsaturated groups in one molecule, and the content ratio of the trifunctional ethylenically unsaturated compound is 30 mass % to 197700 / 4477 mass % relative to the total amount of the polymerizable compound. The alkali-soluble resin contains 30% by mass to 45% by mass of a constituent unit derived from styrene based on the total mass of all constituent units. The thickness of the photosensitive resin layer is 5 μm to 15 μm. After the photosensitive resin layer is attached to a transfer substrate and exposed to light with an exposure amount Ep, when 10 μL of a 10% by mass aqueous solution of monoethanolamine at 50° C. is dropped onto the surface of the cured layer with the temporary support peeled off, the swelling ratio of the cured layer in the normal direction of the transfer substrate from the start of dropping of the 10% by mass aqueous solution of monoethanolamine to the time point when 10 seconds have passed is 103% or less, Ep=2×Eb, Ep is expressed in mJ / cm 2 The exposure amount in units of mJ / cm 2 After the photosensitive resin layer was attached to the transfer substrate, a high-pressure mercury lamp was used through a mask with 15-step wedges at an illumination of 20 mW / cm 2 The exposure is performed at an exposure amount of an order of magnitude that a residual film after the temporary support is peeled off and developed has a residual thickness of ±1% relative to the thickness of the photosensitive resin layer.

2. The photosensitive transfer material according to claim 1, wherein The swelling ratio of the solidified layer in the normal direction of the transferred substrate at the time point when 20 seconds have passed since the start of the dropping is 105% or less.

3. The photosensitive transfer material according to claim 1 or 2, wherein The alkali-soluble resin contains 30% by mass to 35% by mass of structural units derived from styrene based on the total mass of all structural units.

4. The photosensitive transfer material according to claim 1 or 2, wherein The content ratio of the trifunctional ethylenically unsaturated compound is 40% by mass to 197700 / 4477% by mass relative to the total amount of the polymerizable compound.

5. The photosensitive transfer material according to claim 1 or 2, wherein The photosensitive resin layer has a thickness of 5 μm to 10 μm.

6. The photosensitive transfer material according to claim 1 or 2, wherein The time t in seconds from the time when at least the cured layer after exposure and the transfer substrate are immersed in a 10 mass % aqueous solution of monoethanolamine at 50° C. to the time when the cured layer is completely peeled off from the transfer substrate is completed. 50 and The time t in seconds from the time when at least the cured layer after exposure and the transfer substrate are immersed in a 10 mass % aqueous solution of monoethanolamine at 25° C. to the time when the cured layer is completely peeled off from the transfer substrate is completed. 25 Satisfying the following formula (A1) and the following formula (A2), t 50 ≤60 and t 25 ≤180 (A1), 1≤t 25 / t 50 ≤3 (A2)。 7. A photosensitive transfer material comprising a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator on a temporary support, The polymerizable compound contains a bifunctional ethylenically unsaturated compound having two ethylenically unsaturated groups in one molecule and a trifunctional ethylenically unsaturated compound having three ethylenically unsaturated groups in one molecule, and the content ratio of the trifunctional ethylenically unsaturated compound is 30 mass % to 197700 / 4477 mass % relative to the total amount of the polymerizable compound. The alkali-soluble resin contains 30% by mass to 45% by mass of a constituent unit derived from styrene based on the total mass of all constituent units. The thickness of the photosensitive resin layer is 5 μm to 15 μm. After the photosensitive resin layer is attached to the transfer substrate and exposed to light with an exposure amount Ep, when at least the cured layer and the transfer substrate are immersed in a 10 mass % aqueous solution of monoethanolamine at 25° C. with the temporary support peeled off, the cured layer is peeled off from the transfer substrate by itself, Ep=2×Eb, Ep is expressed in mJ / cm 2 The exposure amount in units of mJ / cm 2 After the photosensitive resin layer was attached to the transfer substrate, a high-pressure mercury lamp was used through a mask with 15-step wedges at an illumination of 20 mW / cm 2 The exposure is performed at an exposure amount of an order of magnitude that a residual film after the temporary support is peeled off and developed has a residual thickness of ±1% relative to the thickness of the photosensitive resin layer.

8. The photosensitive transfer material according to claim 7, wherein The solidified layer is peeled off from the transferred substrate by itself, and is curled with the side of the solidified layer opposite to the side facing the transferred substrate as the inner side.

9. The photosensitive transfer material according to claim 7 or 8, wherein The alkali-soluble resin contains 30% by mass to 35% by mass of structural units derived from styrene based on the total mass of all structural units.

10. The photosensitive transfer material according to claim 7 or 8, wherein The content ratio of the trifunctional ethylenically unsaturated compound is 40% by mass to 197700 / 4477% by mass relative to the total amount of the polymerizable compound.

11. The photosensitive transfer material according to claim 7 or 8, wherein The photosensitive resin layer has a thickness of 5 μm to 10 μm.

12. The photosensitive transfer material according to claim 7 or 8, wherein During the immersion, the time from the immersion of at least the solidified layer and the transfer substrate to the start of the self-peeling of the solidified layer from the transfer substrate is within 300 seconds.

13. A photosensitive transfer material comprising a photosensitive resin layer containing an alkali-soluble resin, a polymerizable compound and a photopolymerization initiator on a temporary support, The polymerizable compound contains a bifunctional ethylenically unsaturated compound having two ethylenically unsaturated groups in one molecule and a trifunctional ethylenically unsaturated compound having three ethylenically unsaturated groups in one molecule, and the content ratio of the trifunctional ethylenically unsaturated compound is 30 mass % to 197700 / 4477 mass % relative to the total amount of the polymerizable compound. The alkali-soluble resin contains 30% by mass to 45% by mass of a constituent unit derived from styrene based on the total mass of all constituent units. The thickness of the photosensitive resin layer is 5 μm to 15 μm. After the photosensitive resin layer is attached to the transfer substrate and exposed to light with an exposure amount Ep, the time t from the time when at least the cured layer and the transfer substrate are immersed in a 10 mass % aqueous solution of monoethanolamine at 50° C. to the time when the cured layer is completely peeled off from the transfer substrate is 100 μm. fr and After the photosensitive resin layer is attached to the transfer substrate and exposed to light at an exposure amount Ep, in a state where the temporary support is peeled off, a time t from the time when at least the cured layer and the transfer substrate are immersed in a 50° C. aqueous solution into which carbon dioxide is blown at a flow rate of 46 mL / min for 160 seconds in 1000 mL of a 10 mass % aqueous solution of monoethanolamine to the time when the cured layer is peeled off from the transfer substrate is completed. fa Satisfies the following formula (B1), t fa ≤t fr ×1.5 (B1), Ep=2×Eb, Ep is expressed in mJ / cm 2 The exposure amount in units of mJ / cm 2 After the photosensitive resin layer was attached to the transfer substrate, a high-pressure mercury lamp was used through a mask with 15-step wedges at an illumination of 20 mW / cm 2 The exposure is performed at an exposure amount of an order of magnitude that a residual film after the temporary support is peeled off and developed has a residual thickness of ±1% relative to the thickness of the photosensitive resin layer.

14. The photosensitive transfer material according to claim 13, wherein The alkali-soluble resin contains 30% by mass to 35% by mass of structural units derived from styrene based on the total mass of all structural units.

15. The photosensitive transfer material according to claim 13, wherein The content ratio of the trifunctional ethylenically unsaturated compound is 40% by mass to 197700 / 4477% by mass relative to the total amount of the polymerizable compound.

16. The photosensitive transfer material according to claim 13, wherein The photosensitive resin layer has a thickness of 5 μm to 10 μm.

17. The photosensitive transfer material according to any one of claims 1, 2, 7, 8 or 13, wherein The difunctional or higher-functional compound having two or more ethylenically unsaturated groups in one molecule includes a compound represented by the following formula (1): In formula (1), R1 and R2 each independently represent a hydrogen atom or a methyl group, A represents C2H4, B represents C3H6, n1 and n3 each independently represent an integer of 1 to 39, and n1+n3 is an integer of 2 to 40, n2 and n4 each independently represent an integer of 0 to 29, and n2+n4 is an integer of 0 to 30, and the arrangement of repeating units of -(AO)- and -(BO)- is random or block. In the case of a block arrangement, any of -(AO)- and -(BO)- is optionally a biphenyl side.

18. A method for manufacturing a resin pattern, comprising: A step of laminating the photosensitive transfer material according to any one of claims 1 to 17 to a substrate to be transferred, and disposing a photosensitive resin layer on the substrate to be transferred; A step of exposing the photosensitive resin layer to a pattern; and A step of developing the photosensitive resin layer to form a resin pattern.

19. A method for manufacturing a circuit wiring, comprising: A step of laminating the photosensitive transfer material according to any one of claims 1 to 17 to a transfer substrate having a conductive layer, and disposing a photosensitive resin layer on the transfer substrate; A step of exposing the photosensitive resin layer to a pattern; A step of developing the photosensitive resin layer to form a resin pattern; A step of etching the conductive layer in a region where the resin pattern is not disposed to form a circuit wiring; and A process of peeling off and removing the resin pattern.

Citation Information

Patent Citations

  • switch

    JP1988250030A

  • Optical switch device

    JP1989140133A

  • Air-conditioning machine for window

    JP1989200125A

  • Unmanned carrier vehicle controller

    JP1990090210A

  • Photosensitive transfer material and image forming method

    JP1993072724A